resin composition

JP2026167527APending Publication Date: 2026-10-14AJINOMOTO CO INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026041896
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-16
Publication Date
2026-10-14

Smart Images

  • Figure 2026167527000001
    Figure 2026167527000001
  • Figure 2026167527000002
    Figure 2026167527000002
  • Figure 2026167527000003
    Figure 2026167527000003
Patent Text Reader

Abstract

This invention provides a resin composition that yields a cured product that simultaneously achieves excellent dielectric properties (low dielectric loss tangent), a low coefficient of linear thermal expansion, high elongation (high elongation at fracture), and excellent crack resistance. [Solution] (A) Epoxy resin, (B) Active ester resin, and (C) Maleimide resin, A resin composition containing, (C) The maleimide resin comprises a (C1) aromatic ring having an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and a (C2) maleimide resin that does not have an aromatic ring, or has an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of more than 0.25. A resin composition in which the ratio of the total number of moles of active groups of component (B) to the total number of moles of active groups of component (A) [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is 1.3 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a resin composition. Furthermore, it relates to a resin sheet, a cured product, a circuit board, and a semiconductor device obtained using the resin composition. [Background technology]

[0002] Resin compositions containing epoxy resins have been widely used as insulating materials for circuit boards such as printed circuit boards and redistribution boards for semiconductor packages because they produce cured products with excellent insulating properties.

[0003] On the other hand, with the increasing speed of communications in recent years, insulating materials for circuit boards require insulating materials with excellent dielectric properties (low dielectric loss tangent) in order to reduce transmission loss when operating in high-frequency environments. As insulating materials with excellent dielectric properties, those employing specific curing agents such as activated ester resins that can reduce or suppress the generation of polar groups such as secondary hydroxyl groups during the curing reaction of epoxy resins have been reported (for example, Patent Documents 1 and 2). [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Patent No. 6992333 [Patent Document 2] Japanese Patent Publication No. 2010-90238 [Overview of the project] [Problems that the invention aims to solve]

[0005] With the evolution of high-speed communication, signal frequencies are expected to increase even further in the future. Organic materials tend to have an increased dielectric loss tangent as the frequency and temperature increase, and in order to achieve low transmission loss even in such environments, it is necessary to keep the dielectric loss tangent even lower. Furthermore, it is required that the material exhibits these dielectric properties while also possessing process compatibility. Process compatibility includes a low coefficient of linear thermal expansion and excellent crack resistance.

[0006] As described above, when using active ester resins or the like as curing agents to obtain cured products with low dielectric loss tangent, low dielectric loss tangent can be achieved even at high frequencies and high temperatures. However, the inventors have confirmed that as the dielectric loss tangent decreases, the linear thermal expansion coefficient and crack resistance may deteriorate. Here, it is conceivable to use maleimide resin to simultaneously achieve low dielectric loss tangent, low linear thermal expansion coefficient, and excellent crack resistance. However, the inventors have confirmed that when attempting to obtain cured products with excellent dielectric properties (low dielectric loss tangent) and linear thermal expansion coefficient by controlling the type of maleimide resin, the resulting cured products may have low crack resistance and elongation. Furthermore, the inventors have confirmed that when attempting to obtain cured products with excellent dielectric properties (low dielectric loss tangent) and crack resistance by controlling the type of maleimide resin, the resulting cured products may have deteriorated linear thermal expansion coefficient and smear removal properties.

[0007] The present invention has been made in view of the above problems, and aims to provide a resin composition that yields a cured product that simultaneously achieves excellent dielectric properties (low dielectric loss tangent), a low coefficient of linear thermal expansion, high elongation (high elongation at fracture), and excellent crack resistance. [Means for solving the problem]

[0008] As a result of intensive studies by the present inventors, the present inventors have found that the above problems can be solved by a resin composition containing (A) an epoxy resin, (B) an active ester resin, and (C) a maleimide resin, wherein component (C) comprises (C1) a maleimide resin having an aromatic ring and having a ratio of the number of dimer diamine skeletons to the number of aromatic rings (dimer diamine / aromatic ring) of 0.25 or less, and (C2) a maleimide resin having no aromatic ring, or having an aromatic ring and having a ratio of the number of dimer diamine skeletons to the number of aromatic rings (dimer diamine / aromatic ring) of more than 0.25, and the ratio of the total number of moles of active groups in component (B) to the total number of moles of active groups in component (A) [total number of moles of active groups in component (B) / total number of moles of active groups in component (A)] is 1.3 or more, thereby completing the present invention.

[0009] That is, the present invention includes the following contents. <1> (A) an epoxy resin, (B) an active ester resin, and (C) a maleimide resin, The resin composition comprising Component (C) comprises (C1) a maleimide resin having an aromatic ring and having a ratio of the number of dimer diamine skeletons to the number of aromatic rings (dimer diamine / aromatic ring) of 0.25 or less, and (C2) a maleimide resin having no aromatic ring, or having an aromatic ring and having a ratio of the number of dimer diamine skeletons to the number of aromatic rings (dimer diamine / aromatic ring) of more than 0.25, A resin composition, wherein the ratio of the total number of moles of active groups in component (B) to the total number of moles of active groups in component (A) [total number of moles of active groups in component (B) / total number of moles of active groups in component (A)] is 1.3 or more. <2> The resin composition according to <1>, wherein the content of component (A) is 15 to 30 mass% when the resin component in the resin composition is taken as 100 mass%. <3> The resin composition according to <1> or <2>, wherein the content of component (B) is 10 to 70 mass% when the resin component in the resin composition is taken as 100 mass%. <4> The content of component (C1) is 1 to 30% by mass, when the total amount of resin components in the resin composition is considered to be 100% by mass. <1> ~ <3> A resin composition as described in any of the following. <5> The content of component (C2) is 1 to 20% by mass, when the total amount of resin components in the resin composition is considered to be 100% by mass. <1> ~ <4> A resin composition as described in any of the following. <6> The mass ratio of component (C1) to component (C2) [(C1) component / (C2) component] is between 0.01 and 100. <1> ~ <5> A resin composition as described in any of the following. <7> Component (C2) contains a maleimide resin represented by the following formula (C2-1): <1> ~ <6> A resin composition as described in any of the following. [ka] (In the formula, n represents a non-negative integer, and * represents a combination.) <8> Furthermore, (D) containing inorganic fillers, <1> ~ <7> A resin composition as described in any of the following. <9> Furthermore, (E) containing organic fillers, <1> ~ <8> A resin composition as described in any of the following. <10> Furthermore, (F) containing thermoplastic resin, <1> ~ <9> A resin composition as described in any of the following. <11> Furthermore, (G) contains a curing accelerator, <1> ~ <10> A resin composition as described in any of the following. <12> The dielectric loss tangent (Df) of the cured resin composition is less than 0.0050 when measured at 150 GHz and 90°C. <1> ~ <11> A resin composition as described in any of the following. <13> It is for the insulating layer of a circuit board. <1> ~ <12> A resin composition as described in any of the following. <14> A support and provided on the support <1> ~ <13> A resin sheet comprising a layer of the resin composition described in any of the following. <15> The support is a thermoplastic resin film or a metal foil. <14> The resin sheet described above. <16> <1> ~ <13> A cured product of any of the resin compositions described above. <17> <1> ~ <13> A circuit board comprising an insulating layer having a cured product of any of the resin compositions described above. <18> <17> A semiconductor device including the circuit board described above. [Effects of the Invention]

[0010] According to the present invention, it is possible to provide a resin composition that yields a cured product that simultaneously achieves excellent dielectric properties (low dielectric loss tangent), a low coefficient of linear thermal expansion, high elongation (high elongation at fracture), and excellent crack resistance, as well as a resin sheet, cured product, circuit board, and semiconductor device obtained using the resin composition. [Modes for carrying out the invention]

[0011] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples listed below, and may be implemented with modifications as appropriate without departing from the scope of the claims and their equivalents.

[0012] [Explanation of terms] In the following explanation, the notations "XX or greater and YY or less" or "XX~YY" that represent numerical ranges mean a numerical range that includes the lower and upper limits, unless otherwise specified. When numerical ranges are described in steps, the upper and lower limits of each numerical range can be combined in any way.

[0013] In the following explanation, "non-volatile components" refers to the components of the resin composition other than the organic solvents described later. Furthermore, "resin components" refers to the non-volatile components of the resin composition, excluding the inorganic fillers described later.

[0014] In the following description, "aromatic ring" refers to a ring that obeys Hückel's rule, where the number of electrons in the π-electron system on the ring is 4r+2 (where r is a natural number), and includes monocyclic aromatic rings and fused aromatic rings formed by the fusion of two or more monocyclic aromatic rings. Unless otherwise specified, monocyclic aromatic rings are preferred as aromatic rings. Aromatic rings can be aromatic carbocyclic rings having only carbon atoms as ring constituent atoms, or aromatic heterocyclic rings having heteroatoms such as oxygen, nitrogen, or sulfur atoms in addition to carbon atoms as ring constituent atoms. Unless otherwise specified, aromatic carbocyclic rings are preferred as aromatic rings. Unless otherwise specified, the number of carbon atoms in an aromatic ring is preferably 3 or more, more preferably 4 or more or 5 or more, and even more preferably 6 or more, with an upper limit of preferably 24 or less, more preferably 18 or less or 14 or less, and even more preferably 10 or less. The number of carbon atoms of substituents is not included in the number of carbon atoms.

[0015] Examples of monocyclic aromatic rings include benzene rings, furan rings, thiophene rings, pyrrole rings, pyrazole rings, oxazole rings, isoxazole rings, furazan rings, thiazole rings, isothiazole rings, thiadiazole rings, imidazole rings, triazole rings, tetrazole rings, pyridine rings, pyridazine rings, pyrimidine rings, pyrazine rings, and pyridazine rings. Examples of condensed aromatic rings formed by the fusion of two or more monocyclic aromatic rings include naphthalene rings, anthracene rings, phenanthrene rings, benzofuran rings, isobenzofuran rings, indole rings, isoindole rings, benzothiophene rings, benzimidazole rings, indazole rings, benzoxazole rings, benzoisoxazole rings, benzothiazole rings, quinoline rings, isoquinoline rings, quinoxaline rings, acridine rings, quinazoline rings, sinnoline rings, phthalazine rings, pyridothiazole rings, benzotriazole rings, imidazopyridine rings, triazopyridine rings, and purine rings. Unless otherwise specified, benzene rings or naphthalene rings are preferred as aromatic rings, with benzene rings being more preferred.

[0016] [Resin composition] The resin composition of the present invention is a resin composition comprising (A) an epoxy resin, (B) an active ester resin, and (C) a maleimide resin, wherein component (C) comprises (C1) a maleimide resin having aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and (C2) a maleimide resin that does not have aromatic rings, or has aromatic rings and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of greater than 0.25, and the ratio of the total number of moles of active groups of component (B) to the total number of moles of active groups of component (A) [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is 1.3 or more. By combining components (A), (B), (C1), and (C2) in a resin composition and controlling the ratio [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] within a specific range, it is possible to obtain a cured product that simultaneously achieves excellent dielectric properties (low dielectric loss tangent), a low coefficient of linear thermal expansion, high elongation (high elongation at breaking point), and excellent crack resistance. The inventors have also confirmed that the cured product obtained by the present invention exhibits a low dielectric loss tangent even under high frequency (150 GHz) and high temperature (90°C) environments, and has excellent adhesion to the underlying copper (underlying copper adhesion) and smear removal properties.

[0017] The resin composition of the present invention may contain any additional components in combination with components (A), (B), and (C). Examples of optional components include (D) inorganic fillers, (E) organic fillers, (F) thermoplastic resins, (G) curing accelerators, (H) organic solvents, (I) other additives, etc. The components contained in the resin composition of the present invention will be described in detail below.

[0018] <(A) Epoxy resin> The resin composition of the present invention contains (A) epoxy resin. The epoxy resin is a curable resin having epoxy groups and an epoxy equivalent of 5,000 g / eq. or less. By containing (A) epoxy resin in combination with (B) active ester resin, which will be described later, it is possible to obtain a cured product that maintains a low dielectric loss tangent Df, has a low coefficient of linear thermal expansion, exhibits high elongation, and has excellent crack resistance. (A) epoxy resin may be used alone or in combination of two or more types. In one embodiment, it is preferable to use two or more types of (A) epoxy resin in combination.

[0019] (A) The epoxy resin is not particularly limited in type, as long as it has one or more (preferably two or more) epoxy groups in one molecule. (A) Examples of epoxy resins include bixylenol type epoxy resin, bisphenol type epoxy resin (bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol C type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, etc.), dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, biphenyl aralkyl type Examples include epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiroring-containing epoxy resins, cyclohexane-type epoxy resins, cyclohexanedimethanol-type epoxy resins, naphthylene ether-type epoxy resins, trimethylol-type epoxy resins, tetraphenylethane-type epoxy resins, isocyanurate-type epoxy resins, phenolphthaleimidine-type epoxy resins, glycirol-type epoxy resins, alkylene oxy-backbone-containing epoxy resins, fluorene-structure-containing epoxy resins, halogenated epoxy resins, resorcinol-type epoxy resins, etc. Bisphenol-type epoxy resins, naphthalene-type epoxy resins, or biphenyl-type epoxy resins are preferred, and naphthalene-type epoxy resins or biphenyl-type epoxy resins are more preferred. In one embodiment, component (A) preferably includes an epoxy resin having an aromatic backbone.

[0020] The resin composition of the present invention preferably contains an epoxy resin having two or more epoxy groups in one molecule as component (A). From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of epoxy resin (A) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0021] (A) Epoxy resins include epoxy resins that are liquid at 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at 20°C (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resin as component (A), only solid epoxy resin, or a combination of liquid epoxy resin and solid epoxy resin. In one embodiment, the resin composition of the present invention preferably contains a combination of liquid epoxy resin and solid epoxy resin.

[0022] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.

[0023] Examples of liquid epoxy resins include glycirol-type epoxy resins, bisphenol-type epoxy resins (bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol C-type epoxy resins, bisphenol AF-type epoxy resins, etc.), naphthalene-type epoxy resins, glycidyl ester-type epoxy resins, glycidylamine-type epoxy resins, phenol novolac-type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexanedimethanol-type epoxy resins, cyclic aliphatic glycidyl ethers, epoxy resins having a butadiene structure, dicyclopentadiene-type epoxy resins, alkylene oxy-skeleton-containing epoxy resins, fluorene-containing epoxy resins, and resorcinol-type epoxy resins. Bisphenol-type epoxy resins or naphthalene-type epoxy resins are preferred, and naphthalene-type epoxy resins are more preferred.

[0024] Specific examples of liquid epoxy resins include "EX-992L" from Nagase ChemteX, "YX7400" from Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP-4032SS" (naphthalene-type epoxy resin) from DIC Corporation; "828US", "jER828EL", "828EL", "825", and "Epicoat 828EL" from Mitsubishi Chemical Corporation; and "850S" (bisphenol A-type epoxy resin) from DIC Corporation; as well as "jER" from Mitsubishi Chemical Corporation. 807, 1750 (Bisphenol F type epoxy resin); Mitsubishi Chemical's "jER152" (Phenol novolac type epoxy resin); Mitsubishi Chemical's "630", "630LSD", "604" (Glycidylamine type epoxy resin); ADEKA's "ED-523T" (Glysilol type epoxy resin); ADEKA's "EP-3950L", "EP-3980S" (Glycidylamine type epoxy resin); ADEKA's "EP-40 88S (dicyclopentadiene type epoxy resin); "ZX-1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Co., Ltd.; "EX-991L" (alkylene oxy skeleton-containing epoxy resin) manufactured by Nagase ChemteX Co., Ltd.; "Celoxide 2021P" (alicyclic epoxy resin with ester skeleton) manufactured by Daicel Corporation. Examples include: resins; "PB-3600" from Daicel Corporation; "JP-100" and "JP-200" from Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" from Nippon Steel Chemical & Material Co., Ltd. (liquid 1,4-glycidylcyclohexane type epoxy resins); "EG-280" from Osaka Gas Chemical Co., Ltd. (fluorene structure-containing epoxy resin); and "EX-201" from Nagase ChemteX Corporation (resorcinol type epoxy resin). These may be used individually or in combination of two or more types.

[0025] As the solid epoxy resin, a solid epoxy resin having two or more epoxy groups per molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups per molecule is more preferred.

[0026] Examples of solid epoxy resins include bixylenol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, naphthol novolac-type epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, triphenylmethane-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, biphenyl aralkyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol-type epoxy resins (bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, etc.), phenol aralkyl-type epoxy resins, tetraphenylethane-type epoxy resins, phenolphthaleimidine-type epoxy resins, and fluorene structure-containing epoxy resins. Biphenyl aralkyl-type epoxy resins or biphenyl-type epoxy resins are preferred, and biphenyl-type epoxy resins are more preferred.

[0027] Specific examples of solid epoxy resins include, for example, DIC's "HP4032H" (naphthalene-type epoxy resin); DIC's "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resins); DIC's "N-690" and "N-695" (cresol novolac-type epoxy resins); DIC's "HP-7200," "HP-7200HH," "HP-7200H," and "HP-7200L" (dicyclopentadiene-type epoxy resins); and DIC's "EXA-7311," "EXA-7311-G3," and "EXA-7311-G4." "EXA-7311-G4S", "HP-6000", "HP-6000L" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-3000", "NC-3000L", "NC-3000FH", "NC-3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-3000H" (biphenyl aralkyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "ESN4" manufactured by Nippon Steel Chemical & Material Co., Ltd. 75V", "ESN4100V" (naphthalene-type epoxy resin); "ESN485" (naphthol-type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene-type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL6121" (biphenyl-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX8800" (anthracene-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; Examples include "YX7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" from Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) from Mitsubishi Chemical Corporation; "YL7800" (fluorene structure-containing epoxy resin) from Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) from Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) from Mitsubishi Chemical Corporation; and "WHR991S" (phenolphthaleinidine type epoxy resin) from Nippon Kayaku Co., Ltd.These may be used individually or in combination of two or more types.

[0028] (A) The epoxy equivalent of the epoxy resin is preferably 50 to 5,000 g / eq. The lower limit of the epoxy equivalent is preferably 50 g / eq. or more, more preferably 60 g / eq. or more, even more preferably 80 g / eq. or more, and particularly preferably 110 g / eq. or more, as mentioned above. The upper limit of the epoxy equivalent is preferably 5,000 g / eq. or less, more preferably 3,000 g / eq. or less, even more preferably 2,000 g / eq. or less, even more preferably 1,000 g / eq. or less, and particularly preferably 500 g / eq. or less, 400 g / eq. or less, or 300 g / eq. or less. The epoxy equivalent is the mass of the epoxy resin containing one equivalent of epoxy groups and can be measured according to JIS K7236.

[0029] (A) The weight-average molecular weight (Mw) of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight-average molecular weight (Mw) of the epoxy resin can be measured as a polystyrene equivalent value by the GPC method.

[0030] The content of (A) epoxy resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or 2% by mass or more, and particularly preferably 3% by mass or 4% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 5% by mass or more, 6% by mass or more, etc. The upper limit is preferably 40% by mass or less or 35% by mass or less, more preferably 30% by mass or less or 25% by mass or less, even more preferably 20% by mass or less, 15% by mass or less or 12% by mass or less, and particularly preferably 10% by mass or less, 9% by mass or less or 8% by mass or less.

[0031] The content of (A) epoxy resin in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or 5% by mass or more, even more preferably 8% by mass or 10% by mass or more, and particularly preferably 12% by mass or 15% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 18% by mass or more, 20% by mass or more, 22% by mass or more, 25% by mass or more, etc. The upper limit is preferably 70% by mass or less or 65% by mass or less, more preferably 60% by mass or less or 55% by mass or less, even more preferably 50% by mass or less or 45% by mass or less, and particularly preferably 40% by mass or less, 35% by mass or less or 30% by mass or less. In one embodiment, the content of (A) epoxy resin is preferably 15 to 30% by mass when the total resin components in the resin composition are considered as 100% by mass.

[0032] <(B) Active ester resin> The resin composition of the present invention contains (B) an activated ester resin. By containing (B) an activated ester resin in the resin composition, the dielectric loss tangent of the cured product can be effectively reduced. (B) an activated ester resin may be used alone or in combination of two or more types.

[0033] (B) As the active ester resin, compounds having one or more active ester groups in one molecule can be used. Among these, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferred as the active ester resin. The active ester resin is preferably obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. In one embodiment, the active ester resin may be an active ester resin obtained from a carboxylic acid compound and a phenol compound or a naphthol compound, or an active ester resin obtained from a carboxylic acid compound and a phenol compound and a naphthol compound.

[0034] Examples of carboxylic acid compounds include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.

[0035] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, phenylphenol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, and phenol novolac. Here, "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by the condensation of two molecules of phenol with one molecule of dicyclopentadiene.

[0036] (B) Preferred specific examples of active ester resins include active ester resins containing a dicyclopentadiene-type diphenol structure (hereinafter also referred to as "dicyclopentadiene-type active ester resin"), active ester resins containing a naphthalene structure, phosphorus-containing active ester resins, active ester resins containing acetylated phenol novolacs, active ester resins containing benzoylated phenol novolacs, and active ester resins containing a butadiene structure. Among these, active ester resins containing a naphthalene structure, active ester resins containing a dicyclopentadiene-type diphenol structure, or active ester resins containing a butadiene structure are preferred, active ester resins containing a naphthalene structure or active ester resins containing a dicyclopentadiene-type diphenol structure are more preferred, and active ester resins containing a dicyclopentadiene-type diphenol structure are even more preferred. "Dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0037] (B) The active ester group equivalent (functional group equivalent) of the active ester resin is preferably 180 g / eq. or more, more preferably 190 g / eq. or more, even more preferably 200 g / eq. or more, and particularly preferably 210 g / eq. or more. The upper limit of the equivalent amount of the active ester group equivalent (functional group equivalent) can be, for example, 1,000 g / eq. or less, 750 g / eq. or less, 700 g / eq. or less, 600 g / eq. or less, 500 g / eq. or less, 400 g / eq. or less, or 300 g / eq. or less.

[0038] (B) Commercially available active ester resins include: Active ester resins containing a dicyclopentadiene-type diphenol structure such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "EXB-8000H", "HPC-8000L-65MT", "EXB-8000L-65TM" (manufactured by DIC); Naphthalene-type active ester resins containing a naphthalene structure such as "EXB-9416-70BK", "EXB-8100L-65T", "EXB-8150L-65T", "HPC-8150-62T", "EXB-8100L-65T", "E Examples include "XB-8" (manufactured by DIC Corporation), "PC1300-02-65T", "PC1300-02-65MA" (manufactured by Air Water Corporation); "EXB-9401" (manufactured by DIC Corporation) as a phosphorus-containing active ester resin; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester resin containing acetylated phenol novolac; and "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and "EXB-8500-65T" (manufactured by DIC Corporation) as active ester resins that are benzoylated phenol novolacs.

[0039] The content of (B) active ester resin in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 7% by mass or more, 8% by mass or more, or 9% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of obtaining the effects of the present invention significantly, and especially from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even under high frequency (150 GHz) and high temperature (90°C) environments. In one embodiment, it may be 10% by mass or more, 11% by mass or more, etc. The upper limit is preferably 40% by mass or less, or 35% by mass or less, more preferably 30% by mass or less, or 25% by mass or less, even more preferably 20% by mass or less, or 18% by mass or less, and particularly preferably 16% by mass or less, 15% by mass or less, or 14% by mass or less.

[0040] The content of (B) active ester resin in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more or 15% by mass or more, even more preferably 20% by mass or more or 25% by mass or more, and particularly preferably 30% by mass or more or 35% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention, and especially from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even under high frequency (150 GHz) and high temperature (90°C) environments. In one embodiment, it may be 40% by mass or more, 45% by mass or more, etc. The upper limit is preferably 90% by mass or less or 85% by mass or less, more preferably 80% by mass or less or 75% by mass or less, even more preferably 70% by mass or less or 65% by mass or less, and particularly preferably 60% by mass or less or 55% by mass or less. In one embodiment, the content of (B) active ester resin is preferably 10 to 70% by mass when the total resin components in the resin composition are considered as 100% by mass.

[0041] The total content of (A) epoxy resin and (B) active ester resin in the resin composition is preferably 2% by mass or more, 5% by mass or more, more preferably 8% by mass or more, 10% by mass or more, and even more preferably 12% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 15% by mass or more, 17% by mass or more, 19% by mass or more, etc. The upper limit is preferably 60% by mass or less or 55% by mass or less, more preferably 50% by mass or less or 45% by mass or less, even more preferably 40% by mass or less, 35% by mass or less or 30% by mass or less, and particularly preferably 25% by mass or less, 23% by mass or less or 21% by mass or less.

[0042] The total content of (A) epoxy resin and (B) active ester resin in the resin composition is preferably 20% by mass or more, more preferably 25% by mass or more or 30% by mass or more, even more preferably 35% by mass or more or 40% by mass or more, and particularly preferably 45% by mass or more or 50% by mass or more, when the total resin component in the resin composition is considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 55% by mass or more, 60% by mass or more, 65% by mass or more, 70% by mass or more, etc. The upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less.

[0043] The mass ratio of component (B) to component (A) in the resin composition [(B) component / (A) component] is preferably 0.1 or more, or 0.3 or more, more preferably 0.5 or more, or 0.8 or more, even more preferably 1.0 or more, or 1.2 or more, and particularly preferably 1.4 or more, or 1.5 or more, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, etc. The upper limit is preferably 10 or less, more preferably 8 or less, or 6 or less, even more preferably 5 or less, or 4 or less, and particularly preferably 3.0 or less, or 2.5 or less. In one embodiment, it may be 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, 2.0 or less, etc.

[0044] As described above, the ratio of the total number of moles of active groups (active ester groups) of component (B) to the total number of moles of active groups (epoxy groups) of component (A) in the resin composition of the present invention [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is 1.3 or more. The ratio [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is preferably 1.4 or more from the viewpoint of obtaining the effects of the present invention in a remarkable manner. Furthermore, from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent), the ratio is more preferably 1.5 or more or 1.6 or more, even more preferably 1.7 or more, and particularly preferably 1.8 or more. The upper limit is preferably 5.0 or less or 4.5 or less, more preferably 4.0 or less or 3.5 or less, even more preferably 3.0 or less, 2.8 or less or 2.6 or less, and particularly preferably 2.5 or less, 2.4 or less or 2.3 or less.

[0045] (C) Maleimide resin The resin composition of the present invention contains (C) maleimide resin. By including (C) maleimide resin in the resin composition, the elongation (elongation at the breaking point) of the cured product can be effectively improved. As described later, in the present invention, two or more types of (C) maleimide resin are used in combination.

[0046] (C) The type of maleimide resin is not particularly limited, as long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrole-1-yl groups) per molecule. Examples of maleimide resins include "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all from Designer Molecules). Maleimide resins containing a 36-carbon aliphatic skeleton derived from dimeramine (manufactured by Inc., etc.); aliphatic maleimide resins such as "SLK-1500-T80" (manufactured by Shin-Etsu Chemical Co., Ltd.), "SLK-6895" (manufactured by Shin-Etsu Chemical Co., Ltd.), and "BMI-TMH" (manufactured by Yamato Kasei Co., Ltd.); maleimide resins containing an indan skeleton as described in the Japan Institute of Invention and Innovation, Technical Report No. 2020-500211; maleimide resins containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT", "MIR-5000-60T" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000", "BMI-2300" (manufactured by Yamato Kasei Co., Ltd.), "BMI-80", and "BMI-70" (manufactured by Kei-I Kasei Co., Ltd.); "BMI-4200" (Designer Molecules Examples include maleimide resins having both a 36-carbon aliphatic skeleton derived from dimer amines (such as those manufactured by Inc.) and an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group; and so on.

[0047] The content of (C) maleimide resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or 2% by mass or more, and particularly preferably 3% by mass or 4% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention, and especially from the viewpoint of further reducing the dielectric loss tangent Df of the cured product. The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less or 12% by mass or less. In one embodiment, it may be 10% by mass or less, 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, etc.

[0048] The content of (C) maleimide resin in the resin composition is preferably 0.5% by mass or more, 1.0% by mass or more, 2% by mass or more, or 5% by mass or more, more preferably 8% by mass or more, or 10% by mass or more, even more preferably 12% by mass or more, or 14% by mass or more, and particularly preferably 15% by mass or more, 16% by mass or more, 17% by mass or more, or 18% by mass or more, when the total resin components in the resin composition are considered as 100% by mass. The upper limit is preferably 70% by mass or less, more preferably 65% ​​by mass or less, even more preferably 60% by mass or less, or 55% by mass or less, and particularly preferably 50% by mass or less, or 45% by mass or less. In one embodiment, it may also be 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, or 22% by mass or less.

[0049] The total content of (A) epoxy resin, (B) active ester resin, and (C) maleimide resin in the resin composition is preferably 2% by mass or more or 5% by mass or more, more preferably 8% by mass or more or 10% by mass or more, even more preferably 12% by mass or more, 15% by mass or more or 18% by mass or more, and particularly preferably 20% by mass or more, 22% by mass or more or 24% by mass or more, when the nonvolatile components in the resin composition are considered to be 100% by mass. There is no particular upper limit, but it may be 100% by mass or less, 90% by mass or less, 80% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, etc.

[0050] The total content of (A) epoxy resin, (B) active ester resin, and (C) maleimide resin in the resin composition is preferably 60% by mass or more or 65% by mass or more, more preferably 70% by mass or more or 75% by mass or more, even more preferably 80% by mass or more or 85% by mass or more, and particularly preferably 90% by mass or more or 95% by mass or more, when the total content of the resin components in the resin composition is considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. There is no particular upper limit, but it may be 100% by mass or less, 99.9% by mass or less, 99.5% by mass or less, 99% by mass or less, 98% by mass or less, 97% by mass or less, etc.

[0051] <(C1) Maleimide resin having an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less> In the resin composition of the present invention, component (C) contains a maleimide resin having an aromatic ring (C1), and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is 0.25 or less. By including component (C1), the dielectric loss tangent of the cured product can be effectively reduced, the linear thermal expansion coefficient of the cured product can be effectively reduced, and the adhesion to the copper substrate (copper substrate adhesion) and smear removal properties can be improved. Component (C1) may be used alone, or two or more types may be used in combination.

[0052] Component (C1) has an aromatic ring. The aromatic ring of component (C1) is as described in the [Explanation of Terms] section and may be either a monocyclic aromatic ring or a fused polycyclic aromatic ring. Furthermore, the aromatic ring may be either an aromatic carbocyclic ring or an aromatic heterocyclic ring.

[0053] From the viewpoint of significantly obtaining the effects of the present invention, the aromatic ring of component (C1) is preferably an aromatic carbocyclic ring. The aromatic carbocyclic ring may be either a monocyclic aromatic carbocyclic ring or a fused polycyclic aromatic carbocyclic ring, and its number of carbon atoms is preferably 6 to 14, more preferably 6 to 10. Therefore, the aromatic ring of component (C1) is preferably an aromatic carbocyclic ring having 6 to 14 carbon atoms, more preferably a benzene ring or a naphthalene ring, and even more preferably a benzene ring.

[0054] Component (C1) may or may not have a dimer amine skeleton. The dimer amine skeleton refers to the carbon skeleton obtained by removing the two terminal amino groups of a dimer amine. Dimer amines can be synthesized from dimer acids. In one embodiment, the number of carbon atoms in the dimer amine skeleton is preferably 36.

[0055] Dimer acids are known compounds obtained by dimerizing unsaturated fatty acids (preferably those with 11 to 22 carbon atoms, more preferably those with 14 to 20 carbon atoms, and especially preferably those with 18 carbon atoms), and their industrial production processes are largely standardized in the industry. Dimer acids that are readily available mainly consist of 36-carbon dimer acids obtained by dimerizing 18-carbon unsaturated fatty acids such as oleic acid and linoleic acid, which are particularly inexpensive and readily available. Dimer acids may also contain arbitrary amounts of monomeric acids, trimer acids, and other polymerized fatty acids, depending on the production method and degree of purification. Furthermore, although double bonds remain after the polymerization reaction of unsaturated fatty acids, in this specification, hydrogenated products obtained by further hydrogenation to reduce the degree of unsaturation are also included as dimer acids.

[0056] In component (C1), the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is 0.25 or less. In this invention, "number of aromatic rings" means the sum of the number of monocyclic aromatic rings and the number of condensed aromatic rings contained in the maleimide resin. That is, for the number of aromatic rings, a condensed aromatic ring is considered as one aromatic ring. For example, one benzene ring contained in the maleimide resin is counted as one aromatic ring, and one naphthalene ring is counted as one aromatic ring. In addition, the number of maleimide rings (maleimide groups) is not included in the number of aromatic rings. For example, in the case of the compound represented by the following formula (Y-1), the number of aromatic rings is 2, and in the case of the compound represented by the following formula (Y-2), the number of aromatic rings is 3.

[0057] [ka]

[0058] In one embodiment, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C1) (dimeramine / aromatic ring) is preferably 0.225 or less, more preferably 0.20 or less, even more preferably 0.175 or less, and particularly preferably 0.15 or less or 0.125 or less. Alternatively, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C1) (dimeramine / aromatic ring) may be 0. That is, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C1) (dimeramine / aromatic ring) can be 0 or more. If component (C1) does not have a dimeramine skeleton, the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is considered to be 0.

[0059] In one embodiment, if component (C1) does not have a dimeramine skeleton, it is preferable that the number of aromatic rings in one molecule of component (C1) is three or more. If component (C1) has a dimeramine skeleton, it is preferable that the number of aromatic rings in one molecule of component (C1) is five or more. That is, it is preferable that component (C1) is a maleimide resin having three or more aromatic rings in the molecule without a dimeramine skeleton, or a maleimide resin having a dimeramine skeleton and five or more aromatic rings in the molecule.

[0060] Specific examples of component (C1) include maleimide resins represented by the following formulas (C-1) to (C-5). Here, for the maleimide resin represented by the following formula (C-4), the number of dimer amine skeletons is m+1, the number of aromatic rings is 4m+8n, and the ratio of the number of elements (dimer amine / aromatic ring) is (m+1) / (4m+8n). Since n≧1, (m+1) / (4m+8n)≦(m+1) / (4m+8)≦(m+1) / (4m+4)=0.25, and the maleimide resin represented by the following formula (C-4) satisfies the requirements of component (C1).

[0061] [ka]

[0062] [ka]

[0063] [ka]

[0064] [ka] (In formula (C-4), X is independently a divalent group having a dimeramine skeleton derived from a dimeramine compound represented by any of the above formulas (a') to (d'), where m≧0 and n≧1. In formulas (a') to (d'), * represents a bond to the nitrogen atom of the maleimide group, and m, n, p, and q are integers of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, respectively. Bonds shown by dashed lines represent carbon-carbon single bonds or carbon-carbon double bonds. However, if a bond shown by a dashed line is a carbon-carbon double bond, the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is one less than the number shown in formulas (a') to (d').)

[0065] [ka]

[0066] The maleimide resin represented by formula (C-4) above is obtained by carrying out an imidation reaction in which a tetracarboxylic acid diacid anhydride is reacted with either a dimer amine compound or a trimer triamine compound, as well as a full orange amine compound, and then maleimidizing the ends. The imidation reaction in the production of the maleimide resin represented by formula (C-4) can be carried out, for example, by referring to Japanese Patent No. 5534378.

[0067] (C1) component may be a commercially available product. Examples of commercially available (C1) component include "MIR-5000-60T" (maleimide resin represented by formula (C-3) above) manufactured by Nippon Kayaku Co., Ltd., "BMI-4200" (maleimide resin represented by formula (C-4) above) manufactured by Designer Molecules Inc., "SLK-2800" (maleimide resin represented by formula (C-4) above) manufactured by Shin-Etsu Chemical Co., Ltd., and "BMI-1000" (maleimide resin represented by formula (C-5) above) manufactured by Yamato Kasei Kogyo Co., Ltd.

[0068] The content of component (C1) in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.2% by mass or more or 0.3% by mass or more, when the nonvolatile components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.5% by mass or more, 0.8% by mass or more, 1.0% by mass or more, 1.2% by mass or more, 1.5% by mass or more, 1.8% by mass or more, 2.0% by mass or more, 2.2% by mass or more, 2.5% by mass or more, 2.8% by mass or more, 3.0% by mass or more, 3.5% by mass or more, 4.0% by mass or more, etc. The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less or 20% by mass or less, even more preferably 15% by mass or less or 12% by mass or less, and particularly preferably 10% by mass or less or 8% by mass or less. In one embodiment, the amount may be 7% by mass or less, 6% by mass or less, 5.0% by mass or less, etc.

[0069] The content of component (C1) in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, 10% by mass or more, 11% by mass or more, 12% by mass or more, 13% by mass or more, 14% by mass or more, 15% by mass or more, 16% by mass or more, etc. The upper limit is preferably 70% by mass or less or 65% by mass or less, more preferably 60% by mass or less or 55% by mass or less, even more preferably 50% by mass or less or 45% by mass or less, and particularly preferably 40% by mass or less, 35% by mass or less or 30% by mass or less. In one embodiment, it may be 25% by mass or less, 20% by mass or less, 18% by mass or less, etc. In one embodiment, the content of component (C1) is preferably 1 to 30% by mass, when the total amount of resin components in the resin composition is 100% by mass.

[0070] The mass ratio of component (C1) to component (A) in the resin composition [(C1) component / (A) component] is preferably 0.001 or higher, more preferably 0.005 or higher, even more preferably 0.01 or higher, and particularly preferably 0.02 or higher or 0.04 or higher, from the viewpoint of significantly obtaining the effects of the present invention, and especially from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even under high frequency (150 GHz) and high temperature (90 °C) environments. In one embodiment, it may be 0.05 or higher, 0.08 or higher, 0.1 or higher, 0.2 or higher, 0.3 or higher, 0.4 or higher, 0.5 or higher, 0.6 or higher, etc. The upper limit is preferably 20 or lower or 15 or lower, more preferably 10 or lower or 8 or lower, even more preferably 5 or lower or 4 or lower, and particularly preferably 3 or lower, 2 or lower or 1.8 or lower. In one embodiment, it may be 1.5 or lower, 1.2 or lower, 1.0 or lower, 0.8 or lower, 0.7 or lower, etc.

[0071] The mass ratio of component (C1) to component (B) in the resin composition [(C1) component / (B) component] is preferably 0.001 or higher, more preferably 0.005 or higher, even more preferably 0.01 or higher, and particularly preferably 0.02 or higher, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.03 or higher, 0.05 or higher, 0.08 or higher, 0.10 or higher, 0.12 or higher, 0.15 or higher, 0.18 or higher, 0.20 or higher, 0.25 or higher, 0.30 or higher, etc. The upper limit is preferably 10 or less or 8 or less, more preferably 5 or less or 4 or less, even more preferably 3 or less or 2 or less, and particularly preferably 1.0 or less or 0.8 or less. In one embodiment, it may be 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.35 or less, etc.

[0072] <(C2) Maleimide resins that do not have aromatic rings, or have aromatic rings, but the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25> In the resin composition of the present invention, component (C) includes a maleimide resin that does not have an aromatic ring (C2), or has an aromatic ring, and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25. By including component (C2), the dielectric loss tangent of the cured product can be effectively reduced, and the crack resistance and elongation (elongation at the breaking point) of the cured product can be effectively improved. Component (C2) may be used alone, or two or more may be used in combination.

[0073] The (C2) component may or may not have an aromatic ring. If the (C2) component has an aromatic ring, the aromatic ring it possesses is as described in the [Explanation of Terms] section and may be either a monocyclic aromatic ring or a fused polycyclic aromatic ring. Furthermore, the aromatic ring may be either an aromatic carbocyclic ring or an aromatic heterocyclic ring.

[0074] When component (C2) has an aromatic ring, from the viewpoint of significantly obtaining the effects of the present invention, it is preferable that the aromatic ring of component (C2) is an aromatic carbon ring. The aromatic carbon ring may be either a monocyclic aromatic carbon ring or a fused polycyclic aromatic carbon ring, and its number of carbon atoms is preferably 6 to 14, more preferably 6 to 10. The aromatic ring of component (C2) is preferably an aromatic carbon ring having 6 to 14 carbon atoms, more preferably a benzene ring or a naphthalene ring, and even more preferably a benzene ring.

[0075] If component (C2) has aromatic rings, component (C2) has a dimeramine skeleton, and the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25. The method for counting the "number of aromatic rings" is as explained in the section "<Maleimide resin having aromatic rings (C1) and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less>". In one embodiment, the ratio of the number of dimeramine skeletons to the number of aromatic rings in component (C2) (dimeramine / aromatic ring) is preferably greater than 0.275 or greater than 0.30, more preferably greater than 0.325 or greater than 0.35, even more preferably greater than 0.375, greater than 0.40 or greater than 0.425, and particularly preferably greater than 0.45, greater than 0.475 or greater than 0.50.

[0076] The dimer amine skeleton of component (C2) is the same as the dimer amine skeleton described in the section "<(C1) Maleimide resin having an aromatic ring and a ratio of the number of dimer amine skeletons to the number of aromatic rings (dimer amine / aromatic ring) of 0.25 or less>".

[0077] In one embodiment, the number of aromatic rings in one molecule of component (C2) is preferably 4 or less, more preferably 3 or less, and even more preferably 2 or less. Furthermore, the number of aromatic rings in one molecule of component (C2) can be 0 or more. That is, component (C2) is preferably a maleimide resin having a dimer amine skeleton and containing 0 to 4 aromatic rings within the molecule.

[0078] In one embodiment, the (C2) component preferably includes a maleimide resin represented by the following formula (C2-3).

[0079] [ka] (In formula (C2-3), R independently represents a divalent hydrocarbon group containing a dimer amine skeleton. n represents a non-negative integer.)

[0080] In formula (C2-3), n represents an integer greater than or equal to 0. The upper limit of n is preferably 10 or less or 9 or less, more preferably 8 or less or 7 or less, even more preferably 6 or less or 5 or less, and particularly preferably 4 or less, 3 or less or 2 or less. The lower limit of n may be 1 or more. Also, n may be 0, 1 or 2.

[0081] In formula (C2-3), each R independently represents a divalent hydrocarbon group containing a dimer amine skeleton. R preferably has 36 carbon atoms.

[0082] In one embodiment, R is preferably a divalent group represented by the following formula (2) or (3).

[0083] [ka] (In equation (2), m1, n1, p1, and q1 are integers greater than or equal to 1. However, m1+n1 is between 6 and 17, and p1+q1 is between 8 and 19. Also, in equation (3), m2, n2, p2, and q2 are integers greater than or equal to 1. However, m2+n2 is between 6 and 17, and p2+q2 is between 8 and 19. Furthermore, in equations (2) and (3), dashed lines independently represent carbon-carbon single bonds or carbon-carbon double bonds, and * represents a bond to the nitrogen atom of the maleimide group.)

[0084] Among the groups represented by formula (2), the divalent group represented by formula (4) below is more preferred.

[0085] [ka] (In equation (4), the meaning of the symbols is the same as described above.)

[0086] Among these, a more preferred example of R is a divalent group represented by any of the following formulas (2-1) to (2-4) and formulas (3-1) to (3-2).

[0087] [ka] (In equations (2-1) to (2-4) and equations (3-1) to (3-2), the meaning of the symbols is the same as described above.)

[0088] Among these preferred examples, a more preferred example of R is a divalent group represented by any of the following formulas (2-5) to (2-8), (3-3), and (3-4). Of these, the group of formula (2-3) or the group of formula (3-3) is preferred, and the group of formula (2-3) is particularly preferred.

[0089] [ka] (In formulas (2-5) to (2-8), (3-3), and (3-4), * indicates a bond to the nitrogen atom of the maleimide group.)

[0090] Furthermore, a preferred specific example of a divalent group represented by formula (2-5) is the divalent group represented by formula (2-9) below. A preferred specific example of a divalent group represented by formula (2-7) is the divalent group represented by formula (2-10) below.

[0091] [ka] (In formulas (2-9) and (2-10), * represents a bond to the nitrogen atom of the maleimide group.)

[0092] In other words, in one embodiment, the (C2) component preferably includes a maleimide resin represented by the following formula (C2-1).

[0093] [ka] (In the formula, n represents a non-negative integer, and * represents a bond attached to the nitrogen atom of the maleimide group.)

[0094] Specific examples of component (C2) include maleimide resin represented by formula (C2-1) above, and maleimide resins represented by formulas (C2-4) to (C2-6) below. Here, for the maleimide resin represented by formula (C2-1) above, the number of dimeramine skeletons is n+1, the number of aromatic rings is 2n, and the ratio of the number of elements (dimeramine / aromatic ring) is (n+1) / 2n (=1 / 2 + 1 / 2n). Also, for the maleimide resin represented by formula (C2-4) below, the number of dimeramine skeletons is n+1, the number of aromatic rings is n, and the ratio of the number of elements (dimeramine / aromatic ring) is (n+1) / n (=1 + 1 / n). Furthermore, for the maleimide resin represented by the following formula (C2-5), the number of dimer amine skeletons is n+1, the number of aromatic rings is 4n, and the ratio of the number of elements (dimer amine / aromatic ring) is (n+1) / 4n (=1 / 4 + 1 / 4n).

[0095] [ka]

[0096] [ka]

[0097] [ka]

[0098] Component (C2) may be a commercially available product. Examples of commercially available components for component (C2) include "BMI-689" from Designer Molecules Inc. (a maleimide resin represented by the above formula (C2-1) when n=0), "SLK-1500-T80" from Shin-Etsu Chemical Co., Ltd. (a maleimide resin represented by the above formula (C2-1) when n is an integer of 1 or more), "BMI-3000" from Designer Molecules Inc. (a maleimide resin represented by the above formula (C2-4)), and "BMI-1700" from Designer Molecules Inc. (a maleimide resin represented by the above formula (C2-5)).

[0099] The content of component (C2) in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.2% by mass or more or 0.3% by mass or more, when the nonvolatile components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may also be 0.4% by mass or more, 0.5% by mass or more, etc. The upper limit is preferably 30% by mass or less or 25% by mass or less, more preferably 20% by mass or less or 15% by mass or less, even more preferably 12% by mass or less or 10% by mass or less, and particularly preferably 8% by mass or less, 6% by mass or less or 5% by mass or less. In one embodiment, it may also be 4% by mass or less, 3.0% by mass or less, 2.5% by mass or less, 2.0% by mass or less, 1.5% by mass or less, 1.0% by mass or less, 0.8% by mass or less, etc.

[0100] The content of component (C2) in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, when the total resin components in the resin composition are considered as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 1.2% by mass or more, 1.5% by mass or more, 1.8% by mass or more, etc. The upper limit is preferably 50% by mass or less, more preferably 45% by mass or 40% by mass or less, even more preferably 35% by mass or 30% by mass or less, and particularly preferably 25% by mass or 20% by mass or less. In one embodiment, it may be 18% by mass or less, 15% by mass or less, 12% by mass or less, 10% by mass or less, 9% by mass or less, 8% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3.0% by mass or less, 2.5% by mass or less, etc. In one embodiment, the content of component (C2) is preferably 1 to 20% by mass, when the total amount of resin components in the resin composition is 100% by mass.

[0101] The mass ratio of component (C2) to component (A) in the resin composition [(C2) component / (A) component] is preferably 0.001 or higher, more preferably 0.005 or higher, even more preferably 0.01 or higher or 0.02 or higher, and particularly preferably 0.04 or higher or 0.05 or higher, from the viewpoint of significantly obtaining the effects of the present invention, and especially from the viewpoint of obtaining a cured product that exhibits even better dielectric properties (low dielectric loss tangent) even under high frequency (150 GHz) and high temperature (90 °C) environments. In one embodiment, it may be 0.06 or higher, 0.07 or higher, etc. The upper limit is preferably 20 or lower or 15 or lower, more preferably 10 or lower, 8 or lower or 5 or lower, even more preferably 4 or lower, 3 or lower or 2 or lower, and particularly preferably 1.8 or lower, 1.5 or lower or 1.2 or lower. In one embodiment, the values ​​may be 1.0 or less, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less, 0.09 or less, etc.

[0102] The mass ratio of component (C2) to component (B) in the resin composition [(C2) component / (B) component] is preferably 0.001 or higher, more preferably 0.005 or higher, even more preferably 0.01 or higher, and particularly preferably 0.02 or higher, from the viewpoint of significantly obtaining the effects of the present invention. In one embodiment, it may be 0.03 or higher, 0.04 or higher, etc. The upper limit is preferably 10 or less or 8 or less, more preferably 5 or less or 4 or less, even more preferably 3 or less, 2 or less or 1 or less, and particularly preferably 0.8 or less, 0.6 or less or 0.5 or less. In one embodiment, it may be 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less, 0.08 or less, 0.05 or less, etc.

[0103] The mass ratio of component (C1) to component (C2) in the resin composition [(C1) component / (C2) component] is preferably 0.01 or higher, more preferably 0.03 or higher, and even more preferably 0.05 or higher, from the viewpoint of significantly obtaining the effects of the present invention. Furthermore, from the viewpoint of further reducing the coefficient of linear thermal expansion, it is particularly preferably 0.08 or higher, 0.1 or higher, 0.3 or higher, 0.5 or higher, 0.8 or higher, 1.0 or higher, 1.2 or higher, 1.4 or higher, 1.5 or higher, 2.0 or higher, 3 or higher, 4 or higher, or 5 or higher. The upper limit is preferably 100 or less, more preferably 80 or less, and even more preferably 50 or less, or 30 or less, from the viewpoint of significantly obtaining the effects of the present invention. Furthermore, from the viewpoint of obtaining a cured product with even better crack resistance, it is particularly preferably 20 or less, 18 or less, 15 or less, 12 or less, 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less. In one embodiment, the mass ratio of component (C1) to component (C2) [(C1) component / (C2) component] is preferably 0.01 to 100.

[0104] The mass ratio of the content of component (C2) to the total content of components (A) and (B) in the resin composition [(C2) component / ((A) component + (B) component)] is preferably 1.0 or less or 0.8 or less, more preferably 0.5 or less, 0.4 or less or 0.3 or less, even more preferably 0.2 or less, 0.1 or less or 0.08 or less, and particularly preferably 0.06 or less, 0.05 or less or 0.04 or less. In one embodiment, it may be 0.03 or less, 0.025 or less, etc. The lower limit is not particularly limited, but may be 0.001 or more, 0.005 or more, 0.01 or more, etc.

[0105] <(D) Inorganic filler> The resin composition of the present invention may contain (D) an inorganic filler as an optional component, and it is preferable to contain (D) an inorganic filler. By containing (D) an inorganic filler, the linear thermal expansion coefficient and dielectric loss tangent of the cured product can be reduced more effectively.

[0106] (D) Inorganic compounds can be used as the material for the inorganic filler. (D) Examples of inorganic fillers include silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Spherical silica is preferred as the shape of the silica. (D) The inorganic filler may be used alone or in combination of two or more types in any ratio.

[0107] (D) Examples of commercially available inorganic fillers include "SP60-05" and "SP507-05" from Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", "SO-C1", "SC2300-SVJ", "SC2050-SXF", and "180nmSX-C1" from Admatex Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" from Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" from Tokuyama Corporation; "Cellspheres" and "MGH-005" from Taiheiyo Cement Corporation; and "LHP-208" from Ube Eximo Co., Ltd.

[0108] (D) The average particle size of the inorganic filler is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 2 μm or less, even more preferably 1 μm or less, and particularly preferably 0.7 μm or less or 0.6 μm or less, from the viewpoint of making the surface of the cured product (insulating layer) low roughness and facilitating the formation of fine wiring. (D) The lower limit of the average particle size of the inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.15 μm or more, 0.2 μm or more, 0.3 μm or more or 0.4 μm or more. (D) The average particle size of the inorganic filler can be measured by the laser diffraction-scattering method based on Mie scattering theory. Specifically, the particle size distribution of the inorganic filler can be created on a volume basis using a laser diffraction-scattering particle size distribution analyzer, and the average particle size can be measured by taking the median diameter as the average particle size. The measurement sample can be prepared by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing them using ultrasound for 10 minutes. The light source wavelength for the laser diffraction particle size distribution analyzer can be blue or red, and the measurement can be performed using a flow cell method. An example of a laser diffraction particle size distribution analyzer is the "LA-960" manufactured by Horiba, Ltd.

[0109] The specific surface area of the inorganic filler (D) is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5 m 2 / g or more, still more preferably 1 m 2 / g or more or 3 m 2 / g or more. The upper limit of the specific surface area of the inorganic filler (D) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70 m 2 / g or less, still more preferably 50 m 2 / g or less, particularly preferably 40 m 2 / g or less, 30 m 2 / g or less, 20 m 2 / g or less or 10 m 2 / g or less. The specific surface area of the inorganic filler can be calculated according to the BET method by adsorbing nitrogen gas on the sample surface using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) and employing the BET multi-point method.

[0110] (D) The inorganic filler is preferably surface-treated with a surface treatment agent. Surface treatment can improve the moisture resistance and dispersibility of the inorganic filler (D). Examples of surface treatment agents include vinyl silane coupling agents such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; and styryl silane coupling agents such as p-styryltrimethoxysilane. Methacryl silane coupling agents such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane; acrylic silane coupling agents such as 3-acryloxypropyltrimethoxysilane; N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-amino Amino-based silane coupling agents such as propyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-8-aminooctyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane; isocyanurate-based silane coupling agents such as tris(trimethoxysilylpropyl)isocyanurate; 3 -Ureidopropyltrialkoxysilane and other ureidopropyl silane coupling agents; mercaptopropyl silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate silane coupling agents such as 3-isocyanatetopropyltriethoxysilane; acid anhydride silane coupling agents such as 3-trimethoxysilylpropyl succinic anhydride; sulfide silane coupling agents such as bis(triethoxysilylpropyl)tetrasulfide;Examples include silane coupling agents such as methyltrimethoxysilane and phenyltrimethoxysilane, non-silane coupling alkoxysilane compounds, organosilazane compounds, and titanate coupling agents. Furthermore, the surface treatment agent may be used alone or in combination of two or more in any ratio. In one embodiment, (D) the inorganic filler is preferably surface-treated with an amino-based silane coupling agent, and more preferably with N-phenyl-3-aminopropyltrimethoxysilane.

[0111] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment by the surface treatment agent is preferably within a predetermined range. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 to 5 parts by mass of the surface treatment agent, more preferably with 0.2 to 3 parts by mass, and even more preferably with 0.3 to 2 parts by mass.

[0112] The degree of surface treatment by a surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler should be 0.02 mg / m². 2 The above is preferred, and 0.1 mg / m² 2 The above is more preferable, 0.2 mg / m² 2 The above is even more preferable. The upper limit is 1 mg / m². 2 The following is preferred: 0.8 mg / m² 2 The following is more preferable: 0.5 mg / m² 2 The following is even more preferable.

[0113] (D) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after cleaning the inorganic filler with a solvent (e.g., methyl ethyl ketone (MEK)) after surface treatment. Specifically, a sufficient amount of MEK as the solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant liquid and drying the solids, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As a carbon analyzer, a Horiba "EMIA-320V" or similar can be used.

[0114] In one embodiment, the resin composition of the present invention may include a hollow inorganic filler as (D) an inorganic filler. The material of the hollow inorganic filler is as described above for inorganic fillers, and among them, hollow silica, hollow alumina, or hollow aluminosilicate is preferred, and hollow silica is more preferred.

[0115] The average porosity of the hollow inorganic filler is preferably 90 volume% or less, and more preferably 85 volume% or less. The lower limit of the average porosity of the hollow inorganic filler is not particularly limited, but for example, it is greater than 0 volume% and 1 volume% or more, preferably 5 volume% or more, more preferably 10 volume% or more, even more preferably 15 volume% or more, 20 volume% or more, 25 volume% or more, or 30 volume% or more, and particularly preferably 35 volume% or more, 40 volume% or more, or 45 volume% or more. The average porosity P (volume%) of the inorganic filler is defined as the volume-based ratio of the total volume of voids inside the particle to the total volume of the particle based on the outer surface of the particle (total volume of voids / volume of particle). The average porosity P (volume%) of the inorganic filler is, for example, measured D of the actual density (apparent density) of the inorganic filler. M (g / cm 3 ), and the theoretical value D of the material density of the material forming the inorganic filler. T (g / cm 3 It is calculated using the following formula (I).

[0116]

number

[0117] The actual density (apparent density) of inorganic fillers can be measured, for example, using a true density analyzer. An example of a true density analyzer is the "ULTRAPYCNOMETER1000" manufactured by QUANTACHROME. Nitrogen is used as the measurement gas.

[0118] The resin composition of the present invention may contain only a solid inorganic filler as (D), only a hollow inorganic filler, or a combination of a solid inorganic filler and a hollow inorganic filler. In one embodiment, it is preferable that the resin composition of the present invention contains only a solid inorganic filler as (D) the inorganic filler, or a combination of a solid inorganic filler and a hollow inorganic filler.

[0119] The content of (D) inorganic filler in the resin composition is 0% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more or 40% by mass or more, and particularly preferably 50% by mass or more or 60% by mass or more. In one embodiment, it may be 70% by mass or more. The upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less.

[0120] <(E) Organic filler> The resin composition of the present invention may contain (E) an organic filler as an optional component, and it is preferable that it contains (E) an organic filler. (E) The organic filler may be used alone or in combination of two or more types.

[0121] (E) The organic filler is present in particulate form in the resin composition. Examples of (E) organic fillers include rubber particles, polyamide fine particles, silicone particles, and core-shell particles. In the present invention, from the viewpoint of significantly obtaining the desired effects of the present invention, (E) the organic filler preferably contains either rubber particles or core-shell particles, more preferably rubber particles, and even more preferably core-shell rubber particles.

[0122] Examples of rubber components included in rubber particles include olefin-based thermoplastic elastomers such as polybutadiene, polyisoprene, polychlorobutadiene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-diene terpolymer, and ethylene-propylene-butene terpolymer; and acrylic-based thermoplastic elastomers such as propyl poly(meth)acrylate, butyl poly(meth)acrylate, cyclohexyl poly(meth)acrylate, and octyl poly(meth)acrylate; and preferably acrylic-based thermoplastic elastomers. Rubber particles containing an acrylic-based thermoplastic elastomer as a rubber component are called "acrylic rubber particles." Core-shell type particles containing an acrylic-based thermoplastic elastomer as a rubber component are called "acrylic core-shell type particles." Core-shell type rubber particles containing an acrylic thermoplastic elastomer as a rubber component are called "acrylic core-shell type rubber particles." That is, (E) the organic filler preferably contains either acrylic rubber particles or acrylic core-shell type particles, more preferably acrylic rubber particles, and even more preferably acrylic core-shell type rubber particles. Furthermore, the rubber component may be mixed with silicone rubber such as polyorganosiloxane rubber. The rubber component contained in the rubber particles preferably has a glass transition temperature of 0°C or lower, more preferably -10°C or lower, even more preferably -20°C or lower, and particularly preferably -30°C or lower.

[0123] Commercially available rubber particles may be used, such as "EXL-2655" from Dow Chemical Japan, and "Stafyroid AC3401N" and "Stafyroid AC3816N" from Aica Kogyo Co., Ltd. "EXL-2655," "Stafyroid AC3401N," and "Stafyroid AC3816N" also fall under the category of core-shell type rubber particles.

[0124] Core-shell particles are particulate organic fillers having a core particle containing a rubber component as described above and one or more layers of shell covering it. In one embodiment, it is preferable that the core-shell particles are particulate organic fillers consisting of a core particle containing a rubber component as described above and one or more layers of shell covering it. Furthermore, it is preferable that the core-shell particles are core-shell graft copolymer particles having a core particle containing a rubber component as described above and a shell portion formed by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle. It is even more preferable that the core-shell particles are core-shell graft copolymer particles consisting of a core particle containing a rubber component as described above and a shell portion formed by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle. The term "core-shell type" as used here does not necessarily refer only to those in which the core particle and shell portion can be clearly distinguished, but also includes those in which the boundary between the core particle and shell portion is unclear, and the core particle does not have to be completely covered by the shell portion.

[0125] The rubber component is preferably contained in the core-shell type graft copolymer particles at a concentration of 40% by mass or more, more preferably at a concentration of 50% by mass or more, and even more preferably at a concentration of 60% by mass or more. The upper limit of the rubber component content in the core-shell type graft copolymer particles is not particularly limited, but from the viewpoint of sufficiently covering the core particles with the shell portion, it is preferably, for example, 95% by mass or less, or 90% by mass or less.

[0126] Examples of monomer components that form the shell portion of core-shell type graft copolymer particles include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, and glycidyl (meth)acrylate; (meth)acrylic acid; N-substituted maleimides such as N-methylmaleimide and N-phenylmaleimide; maleimides; α,β-unsaturated carboxylic acids such as maleic acid and itaconic acid; aromatic vinyl compounds such as styrene, 4-vinyltoluene, and α-methylstyrene; and (meth)acrylonitrile, with (meth)acrylic acid esters being preferred and methyl (meth)acrylate being more preferred.

[0127] Examples of commercially available core-shell type graft copolymer particles include "CHT" from Samsung SDI; "B602" from Techno UMG; "Paraloid EXL2602", "Paraloid EXL2603", "Paraloid EXL-2655", "Paraloid EXL2311", "Paraloid EXL2313", "Paraloid EXL2315", "Paraloid KM330", "Paraloid KM336P", and "Paraloid KCZ201" from Dow Chemical Japan; "Metabren C-223A", "Metabren E-901", "Metabren S-2001", "Metabren W-450A", and "Metabren SRK-200" from Mitsubishi Chemical Corporation; and "Kaneka M-511", "Kaneka M-600", "Kaneka M-400", "Kaneka M-580", and "Kaneka MR-01" from Kaneka Corporation. These may be used individually or in combination of two or more types.

[0128] The average particle size (average primary particle diameter) of the core-shell type graft copolymer particles is not particularly limited, but is preferably 20 nm or more, more preferably 50 nm or more, even more preferably 80 nm or more, and particularly preferably 100 nm or more. The upper limit is preferably 5,000 nm or less, more preferably 2,000 nm or less, even more preferably 1,000 nm or less, and particularly preferably 500 nm or less. The average particle size (average primary particle diameter) of the core-shell type graft copolymer particles can be measured using a zeta potential particle size distribution analyzer or the like.

[0129] The content of (E) organic filler in the resin composition is 0% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.01% by mass or more or 0.03% by mass or more, more preferably 0.05% by mass or more or 0.08% by mass or more, even more preferably 0.1% by mass or more or 0.2% by mass or more, and particularly preferably 0.3% by mass or more or 0.4% by mass or more. In one embodiment, it may be 0.5% by mass or more, 0.6% by mass or more, etc. The upper limit is preferably 15% by mass or less or 12% by mass or less, more preferably 10% by mass or less or 8% by mass or less, even more preferably 5% by mass or less, 4% by mass or less or 3% by mass or less, and particularly preferably 2% by mass or less, 1.0% by mass or less or 0.8% by mass or less.

[0130] The content of (E) organic filler in the resin composition is 0% by mass or more, when the resin component in the resin composition is taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.05% by mass or more or 0.1% by mass or more, more preferably 0.3% by mass or more or 0.5% by mass or more, even more preferably 0.8% by mass or more or 1.0% by mass or more, and particularly preferably 1.2% by mass or more, 1.5% by mass or more or 1.8% by mass or more. In one embodiment, it may be 2.0% by mass or more, 2.2% by mass or more, 2.4% by mass or more, etc. The upper limit is preferably 30% by mass or less or 25% by mass or less, more preferably 20% by mass or less, 15% by mass or less or 12% by mass or less, even more preferably 10% by mass or less, 8% by mass or less or 6% by mass or less, and particularly preferably 5% by mass or less, 4% by mass or less or 3% by mass or less.

[0131] When the resin composition of the present invention contains (D) an inorganic filler and (E) an organic filler, the mass ratio of component (E) to component (D) in the resin composition [(E) component / (D) component] is preferably 1 × 10 from the viewpoint of significantly obtaining the effects of the present invention. -4 The above is futur3×10 -4 or more, or 5 x 10 -4 More preferably 8 × 10 -4 or more or 1 x 10 -3 In particular, 3 × 10 -3 or more, or 5 x 10 -3 That concludes the explanation. In one embodiment, 8 × 10 -3 The above may be the case. The upper limit is preferably 1 or less or 8 × 10 -1 The following is more preferable: 5 x 10 -1 The following or 3 x 10 -1 More preferably 1 × 10 -1 The following or 8 x 10 -2 The following is particularly preferred: 5 × 10 -2 The following or 3 x 10 -2 The following applies. In one embodiment, 1 × 10 -2 The following are possible options:

[0132] <(F)Thermoplastic resin> The resin composition of the present invention may further contain (F) a thermoplastic resin as an optional component, and it is preferable that it contains (F) a thermoplastic resin.

[0133] Examples of thermoplastic resins include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, and polyester resin. Among these, phenoxy resin is preferred from the viewpoint of significantly obtaining the effects of the present invention. The phenoxy resin described herein is a component other than epoxy resin. Furthermore, thermoplastic resins may be used individually or in combination of two or more types.

[0134] Examples of phenoxy resins include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal end of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0135] Specific examples of phenoxy resins include "1256" and "4250" (both phenoxy resins containing a bisphenol A skeleton) manufactured by Mitsubishi Chemical Corporation; "YX8100" (phenoxy resin containing a bisphenol S skeleton) manufactured by Mitsubishi Chemical Corporation; "YX6954" (phenoxy resin containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation; "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "YL6954BH30", "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0136] Examples of polyvinyl acetal resins include polyvinyl formal resin and polyvinyl butyral resin, with polyvinyl butyral resin being preferred. Specific examples of polyvinyl acetal resins include S-Rec BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, BM series, etc., manufactured by Sekisui Chemical Co., Ltd.

[0137] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0138] Specific examples of polyimide resins include "Ricacoat SN20" and "Ricacoat PN20" manufactured by Shin-Nippon Rika Co., Ltd.

[0139] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Other specific examples of polyamide-imide resins include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Resonaq Corporation.

[0140] Specific examples of polyethersulfone resins include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0141] Specific examples of polysulfone resins include Solvay Advanced Polymers' polysulfones "P1700" and "P3500".

[0142] Examples of polyester resins include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexanedimethyl terephthalate resin.

[0143] The weight-average molecular weight (Mw) of the thermoplastic resin is preferably 8,000 or more, more preferably 10,000 or more, particularly preferably 20,000 or more, preferably 70,000 or less, more preferably 60,000 or less, and particularly preferably 50,000 or less, from the viewpoint of significantly obtaining the effects of the present invention.

[0144] The content of (F) thermoplastic resin in the resin composition is 0% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.001% by mass or 0.003% by mass or more, more preferably 0.005% by mass or 0.008% by mass or more, even more preferably 0.01% by mass or more, 0.03% by mass or more, or 0.05% by mass or more, and particularly preferably 0.08% by mass or more, 0.10% by mass or more, or 0.12% by mass or more. The upper limit is preferably 10% by mass or less, or 8% by mass or less, more preferably 5% by mass or less, or 3% by mass or less, even more preferably 1.0% by mass or less, or 0.8% by mass or less, and particularly preferably 0.5% by mass or less, 0.3% by mass or less, or 0.2% by mass or less.

[0145] The content of (F) thermoplastic resin in the resin composition is 0% by mass or more when the total resin components in the resin composition are considered as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.005% by mass or more or 0.01% by mass or more, more preferably 0.03% by mass or more or 0.05% by mass or more, even more preferably 0.08% by mass or more, 0.1% by mass or more or 0.2% by mass or more, and particularly preferably 0.3% by mass or more, 0.4% by mass or more or 0.5% by mass or more. The upper limit is preferably 30% by mass or less or 25% by mass or less, more preferably 20% by mass or less or 15% by mass or less, even more preferably 10% by mass or less, 5% by mass or less or 3% by mass or less, and particularly preferably 2% by mass or less, 1% by mass or less or 0.8% by mass or less.

[0146] <(G) Curing accelerator> The resin composition of the present invention may contain (G) a curing accelerator as an optional component, and it is preferable that it contains (G) a curing accelerator. By including (G) a curing accelerator, it is possible to obtain a cured product that exhibits better dielectric properties (low dielectric loss tangent) while improving the curability of the resin composition. (G) A curing accelerator may be used alone or in combination of two or more types.

[0147] (G) Examples of curing accelerators include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, triazole-based curing accelerators, metal-based curing accelerators, amine-based curing accelerators, etc. (G) The curing accelerator may be used alone or in combination of two or more types. (G) The curing accelerator preferably contains an amine-based curing accelerator, a triazole-based curing accelerator, or an imidazole-based curing accelerator, and more preferably contains a triazole-based curing accelerator or an imidazole-based curing accelerator. In one embodiment, (G) the curing accelerator is even more preferably a triazole-based curing accelerator.

[0148] Examples of amine-based curing accelerators include trialkylamines such as triethylamine and tributylamine; pyridines such as 4-dimethylaminopyridine; and benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene. Pyridines are preferred, and 4-dimethylaminopyridine is more preferred. These may be used individually or in combination of two or more.

[0149] As amine-based curing accelerators, commercially available products may be used, such as "MY-25" manufactured by Ajinomoto Fine Techno Co., Ltd. and "DMAP" manufactured by Koei Chemical Industry Co., Ltd.

[0150] Examples of phosphorus-based curing accelerators include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium) pyromelitate, tetrabutylphosphonium hydrogen hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, and tetraphenylphosphonium bromide. Aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition products such as triphenylphosphine-p-benzoquinone addition products; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples include aromatic phosphines such as tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether. These may be used individually or in combination of two or more.

[0151] Examples of urea-based curing accelerators include aliphatic dimethylureas such as 1,1-dimethylurea, 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. Aromatic dimethylureas such as toluenebisdimethylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluenebisdimethylurea] are examples. These may be used individually or in combination of two or more.

[0152] Examples of guanidine-based curing accelerators include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]deca-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]deca-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. These may be used individually or in combination of two or more types.

[0153] Examples of imidazole-based curing accelerators include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, and 1-cyanoethyl-2-methylimidazole. , 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6 -[2'-Undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanurate adduct, 2-phenylimidazole isocyanurate adduct, 2-phenyl-4,5-dihydroxymethylimidazole Examples include imidazole compounds such as 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds with epoxy resins, with 1-benzyl-2-phenylimidazole being preferred. These may be used individually or in combination of two or more.

[0154] Examples of commercially available imidazole-based curing accelerators include "1B2PZ", "2P4MZ", "2M4MZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" from Shikoku Chemicals Corporation; and "P200-H50" from Mitsubishi Chemical Corporation. These may be used individually or in combination of two or more.

[0155] Examples of triazole-based curing accelerators include 1,2,3-benzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole, carboxybenzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazole-1-yl)methyl]imino]bisethanol, sodium salt of 1,2,3-benzotriazole, tolyltriazole, etc., with 1,2,3-benzotriazole being preferred. These may be used individually or in combination of two or more.

[0156] Examples of commercially available triazole-based curing accelerators include "BT-120," "BT-120SG," "BT-LX," "CBT-1," "CBT-SG," "TT-LX," "TT-LYK," "JCL-400," and "TT-130F" manufactured by Johoku Chemical Industry Co., Ltd. These may be used individually or in combination of two or more types.

[0157] Examples of metal-based hardening accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate. These may be used individually or in combination of two or more.

[0158] The content of (G) curing accelerator in the resin composition is 0% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.001% by mass or 0.005% by mass or more, more preferably 0.01% by mass or 0.03% by mass or more, even more preferably 0.05% by mass or 0.08% by mass or more, and particularly preferably 0.10% by mass or more, 0.15% by mass or more, or 0.18% by mass or more. The upper limit is preferably 10% by mass or less or 8% by mass or less, more preferably 5% by mass or less or 2% by mass or less, even more preferably 1% by mass or less, 0.8% by mass or less, or 0.5% by mass or less, and particularly preferably 0.4% by mass or less, 0.3% by mass or less, or 0.25% by mass or less.

[0159] The content of (G) curing accelerator in the resin composition is 0% by mass or more when the resin components in the resin composition are considered as 100% by mass. From the viewpoint of significantly obtaining the effects of the present invention, it is preferably 0.01% by mass or more or 0.03% by mass or more, more preferably 0.05% by mass or more or 0.08% by mass or more, even more preferably 0.1% by mass or more or 0.3% by mass or more, and particularly preferably 0.5% by mass or more or 0.7% by mass or more. The upper limit is preferably 20% by mass or less or 15% by mass or less, more preferably 10% by mass or less or 8% by mass or less, even more preferably 5% by mass or less, 4% by mass or less or 3% by mass or less, and particularly preferably 2% by mass or less, 1.5% by mass or less or 1.0% by mass or less.

[0160] <(H) Organic solvents> The resin composition of the present invention may contain an organic solvent (H) as an optional component. The organic solvent (H) may be used alone or in combination of two or more. In one embodiment, it is preferable to use two or more organic solvents (H) in combination.

[0161] (H) Examples of organic solvents include organic solvents composed of atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, phosphorus atoms, sulfur atoms, halogen atoms, and hydrogen atoms. From the viewpoint of safety, (H) organic solvent is preferably an organic solvent composed of atoms selected from carbon atoms, oxygen atoms, and hydrogen atoms, and more preferably an organic solvent composed of carbon atoms, oxygen atoms, and hydrogen atoms.

[0162] Examples of (H) organic solvents include glycol-based organic solvents, glycol ether-based organic solvents, glycol ether ester-based organic solvents, ketone-based organic solvents, ester-based organic solvents, ether-based organic solvents, alcohol-based organic solvents, aliphatic hydrocarbon-based organic solvents, aromatic organic solvents, nitrogen-based organic solvents, sulfur-based organic solvents, halogen-based organic solvents, etc. Examples of nitrogen-based organic solvents include amide-based organic solvents, urea-based organic solvents, nitrile-based organic solvents, etc. From the viewpoint of safety, (H) organic solvents are preferably ester-based organic solvents, ketone-based organic solvents, glycol-based organic solvents, glycol ether-based organic solvents, glycol ether ester-based organic solvents, ketone-based organic solvents, or aromatic organic solvents, more preferably ester-based organic solvents, glycol ether ester-based organic solvents, ketone-based organic solvents, or aromatic organic solvents, even more preferably ketone-based organic solvents or aromatic organic solvents, and particularly preferably ketone-based organic solvents.

[0163] Examples of glycol-based organic solvents include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, and trimethylene glycol.

[0164] Examples of glycol ether-based organic solvents include cellosolves such as ethylene glycol monomethyl ether (also known as methyl cellosolve), ethylene glycol monoethyl ether (also known as cellosolve), ethylene glycol monopropyl ether (also known as propyl cellosolve), ethylene glycol monobutyl ether (also known as butyl cellosolve), ethylene glycol monoisobutyl ether (also known as isobutyl cellosolve), ethylene glycol mono-tert-butyl ether (also known as tert-butyl cellosolve), and ethylene glycol monohexyl ether; diethylene glycol monomethyl ether (also known as methyl carbitol), diethylene glycol monoethyl ether (also known as carbitol), and diethylene glycol monopropyl ether (also known as propyl Examples include carbitols such as carbitol and diethylene glycol monobutyl ether (DB) (also known as butyl carbitol); propylene glycol ethers such as propylene glycol monomethyl ether (PGM, also known as 1-methoxy-2-propanol), propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; and dipropylene glycol ethers such as dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, and dipropylene glycol monobutyl ether. Propylene glycol ethers are preferred, and propylene glycol monomethyl ether (1-methoxy-2-propanol) is more preferred.

[0165] Examples of glycol ether ester organic solvents include cellosolve esters such as ethylene glycol monomethyl ether acetate (also known as methyl cellosolve acetate), ethylene glycol monoethyl ether acetate (also known as cellosolve acetate), and ethylene glycol monobutyl ether acetate (also known as butyl cellosolve acetate); carbitol esters such as diethylene glycol monoethyl ether acetate (EDGAc) (also known as carbitol acetate) and diethylene glycol monobutyl ether acetate (also known as butyl carbitol acetate); propylene glycol ether esters such as propylene glycol monomethyl ether acetate (PGMEAc) and propylene glycol monoethyl ether acetate; and dipropylene glycol ether esters such as dipropylene glycol monomethyl ether acetate. Carbitol esters are preferred, and more preferred than diethylene glycol monoethyl ether acetate.

[0166] Examples of ketone-based organic solvents include aliphatic acyclic ketones such as acetone, methyl ethyl ketone (MEK), diethyl ketone, 2-pentanone, methyl isobutyl ketone, 2-hexanone, 2-heptanone (MAK), and diisobutyl ketone; aliphatic cyclic ketones such as cyclopentanone, cyclohexanone (Anone), and 2-methylcyclohexanone; and aromatic ketones such as acetophenone. Methyl ethyl ketone (MEK) or cyclohexanone are preferred. The lower limit of the number of carbon atoms in the ketone-based organic solvent is preferably 2 or more, more preferably 3 or more, and still more preferably 4 or more. The upper limit of the number of carbon atoms in the ketone-based organic solvent is preferably 10 or less, more preferably 8 or less, and still more preferably 6 or less.

[0167] Ester-based organic solvents are organic solvents having an ester structure that do not fall under the category of glycol ether ester-based organic solvents. Examples include fatty acid alkyl esters such as methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, sec-butyl acetate, tert-butyl acetate, n-pentyl acetate, isopentyl acetate, ethyl propionate, propyl propionate, and isopropyl propionate; alkyl hydroxy acid esters such as methyl lactate, ethyl lactate, and butyl lactate; alkyl keto acid esters such as methyl acetoacetate and ethyl acetoacetate; lactones such as γ-butyrolactone and α-acetyl-γ-butyrolactone; and aromatic esters such as methyl benzoate and ethyl benzoate. Lactones are preferred as ester-based organic solvents. Furthermore, the number of carbon atoms in the ester-based organic solvent is preferably 3 to 9.

[0168] Ether-based organic solvents are organic solvents having an ether structure that do not fall under glycol ether-based organic solvents or glycol ether ester-based organic solvents. Examples include aliphatic acyclic ethers such as dimethyl ether, diethyl ether, methyl ethyl ether, diisopropyl ether, dibutyl ether, methyl tert-butyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether; aliphatic cyclic ethers such as tetrahydrofuran, 1,4-dioxane, and 1,3-dioxolane; and aromatic ethers such as anisole and phenethole. The number of carbon atoms in ether-based organic solvents is preferably 2 to 9.

[0169] Alcohol-based organic solvents are organic solvents having an alcohol structure that do not fall under the category of glycol-based organic solvents or glycol ether-based organic solvents. Examples include aliphatic acyclic alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butyl alcohol, isobutyl alcohol, sec-butyl alcohol, tert-butyl alcohol, n-pentyl alcohol, isopentyl alcohol, sec-pentyl alcohol, tert-pentyl alcohol, neopentyl alcohol, n-hexyl alcohol, n-heptyl alcohol, isoheptyl alcohol, n-octyl alcohol, and 2-ethylhexyl alcohol; aliphatic cyclic alcohols such as cyclohexanol; and aromatic alcohols such as benzyl alcohol and phenethyl alcohol.

[0170] Examples of aliphatic hydrocarbon organic solvents include n-pentane, n-hexane, 2-methylpentane (also known as isohexane), n-heptane, n-octane, cyclopentane, cyclohexane, methylcyclohexane, ethylcyclohexane, and decalin. The number of carbon atoms in the aliphatic hydrocarbon organic solvent is preferably 5 to 10.

[0171] Examples of aromatic organic solvents include benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, etc. 6-8 Aromatic hydrocarbons; C9 aromatic hydrocarbons such as 1,2,3-trimethylbenzene, 1,3,5-trimethylbenzene (also known as mesitylene), 1,2,4-trimethylbenzene, 4-ethyltoluene, 3-ethyltoluene, 2-ethyltoluene; C9 aromatic hydrocarbons such as 1,2-diethylbenzene, 1,3-diethylbenzene, 1,4-diethylbenzene, 3-ethyl-o-xylene, 4-ethyl-o-xylene, 2-ethyl-p-xylene, 1,2,3,5-tetramethylbenzene, tetralin, etc. 10 Aromatic hydrocarbons include aromatic heterocyclic compounds such as pyridine, furan, and thiophene, with toluene being preferred. The aromatic organic solvent preferably has 6 to 10 carbon atoms.

[0172] Examples of amide-based organic solvents include aliphatic acyclic amides such as N,N-dimethylacetamide and N,N-dimethylformamide; lactams such as N-methyl-2-pyrrolidone and N-cyclohexyl-2-pyrrolidone; and phosphate amides such as hexamethylphosphoramide. The number of carbon atoms in the amide-based organic solvent is preferably 2 to 10.

[0173] Examples of urea-based organic solvents include tetramethylurea and 1,3-dimethyl-2-imidazolinone.

[0174] Examples of nitrile-based organic solvents include acetonitrile, propionitrile, and benzonitrile. The number of carbon atoms in the nitrile-based organic solvent is preferably 2 to 10.

[0175] Examples of sulfur-based organic solvents include dimethyl sulfoxide.

[0176] Examples of halogenated organic solvents include chloroform, methylene chloride, carbon tetrachloride, and 1,2-dichloroethane. The halogenated organic solvent preferably has 1 to 10 carbon atoms.

[0177] Among these, the (H) organic solvent is preferably γ-butyrolactone, methyl ethyl ketone (MEK), cyclopentanone, cyclohexanone, propylene glycol, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, or toluene; more preferably methyl ethyl ketone (MEK), cyclohexanone, diethylene glycol monoethyl ether acetate, γ-butyrolactone, propylene glycol monomethyl ether, or toluene; even more preferably methyl ethyl ketone (MEK), cyclohexanone, propylene glycol monomethyl ether, or toluene; and particularly preferably methyl ethyl ketone (MEK) or cyclohexanone.

[0178] The content of (H) organic solvent in the resin composition is 0% by mass or more when the total components in the resin composition are considered as 100% by mass. From the viewpoint of obtaining a varnish with appropriate viscosity, it can be 1% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, 10% by mass or more, 12% by mass or more, 15% by mass or more, etc. The upper limit can be 50% by mass or less, 45% by mass or less, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, etc.

[0179] <(I) Other additives> The resin composition of the present invention may further contain (I) other additives as optional components, to the extent that they do not hinder the objectives of the present invention. Examples of such additives include epoxy resin curing agents other than component (B), such as phenolic curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate ester curing agents, and thiol curing agents; radical polymerizable resins such as (meth)acrylic resins and styryl resins; radical polymerization initiators such as peroxide radical polymerization initiators and azo radical polymerization initiators; organometallic compounds such as organocenium compounds, organozinc compounds, and organocalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium dioxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as bentonite and montmorillonite; and defoaming agents such as silicone defoaming agents, acrylic defoaming agents, fluorine defoaming agents, and vinyl resin defoaming agents. Antifoaming agents; UV absorbers such as benzotriazole-based UV absorbers; adhesion improvers such as urea silane; adhesion ferrants such as triazole-based adhesion ferrants, tetrazole-based adhesion ferrants, and triazine-based adhesion ferrants; antioxidants such as hindered phenol-based antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen Examples of additives include flame retardants such as melamine sulfate, halogenated flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester dispersants, polyoxyalkylene dispersants, acetylene dispersants, silicone dispersants, anionic dispersants, and cationic dispersants; and stabilizers such as borate stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, and carboxylic acid anhydride stabilizers. The content of such additives may be determined according to the properties required of the resin composition.Furthermore, components (A) to (H) may have functions such as epoxy resin curing agents, radical polymerizable resins, radical polymerization initiators, organometallic compounds, colorants, polymerization inhibitors, leveling agents, thickeners, defoamers, ultraviolet absorbers, adhesion enhancers, adhesion-improving agents, antioxidants, fluorescent whitening agents, surfactants, flame retardants, dispersants, and stabilizers. In that case, such components shall be considered as components (A) to (H), rather than component (I).

[0180] <Method for producing resin compositions> The resin composition of the present invention can be prepared by appropriately mixing the necessary components from the above components (A) to (I), and, if necessary, by kneading or mixing with kneading means such as a three-roll mill, ball mill, bead mill, or sand mill, or stirring means such as a super mixer, planetary mixer, or high-speed rotary mixer.

[0181] <Physical properties and applications of resin compositions> In one embodiment, the cured product of the resin composition of the present invention exhibits a low dielectric loss tangent (Df) even at high frequencies and high temperatures. For example, as described in the section "<Evaluation Example 1: Measurement of Dielectric Loss Tangent>" below, when measured at a measurement frequency of 150 GHz and a measurement temperature of 90°C, the dielectric loss tangent (Df) of the cured product of the resin composition of the present invention is preferably less than 0.0100 or less than 0.0080, more preferably less than 0.0060, even more preferably less than 0.0050, and particularly preferably less than 0.0045. The lower limit is not particularly limited, but can be 0.0001 or higher, 0.0010 or higher, etc.

[0182] In one embodiment, the cured product of the resin composition of the present invention exhibits a low coefficient of linear thermal expansion (CTE). For example, as described in the section "<Evaluation Example 2: Measurement of Coefficient of Linear Thermal Expansion (CTE)>" below, when measured using a thermomechanical analyzer, the coefficient of linear thermal expansion (CTE) of the cured product of the resin composition of the present invention is preferably less than 40 ppm / °C or less than 35 ppm / °C, more preferably less than 30 ppm / °C, even more preferably less than 25 ppm / °C, and particularly preferably less than 22 ppm / °C. The lower limit is not particularly limited, but can be 0.1 ppm / °C or higher, 1 ppm / °C or higher, 3 ppm / °C or higher, etc.

[0183] In one embodiment, the cured product of the resin composition of the present invention exhibits a high elongation rate (high elongation at the breaking point). For example, as described in the section "<Test Example 6: Measurement of Elongation Rate (Elongation at Breaking Point)>" below, when tensile strength measurement is performed using a tensile testing machine, the elongation at the breaking point of the cured product of the resin composition of the present invention is preferably 1.0% or more or 1.2% or more, more preferably 1.5% or more, 1.6% or more or 1.7% or more, and even more preferably 1.8% or more, 1.9% or more or 2.0% or more. The upper limit is not particularly limited, but it can be 100% or less, 50% or less, 10% or less, etc.

[0184] In one embodiment, the cured product of the resin composition of the present invention exhibits high adhesion to the underlying copper. For example, the load used when measuring the peel strength, as described in the section "<Evaluation Example 3: Evaluation Test of Adhesion to Underlying Copper>" below, is preferably 0.30 kgf / cm or more or 0.40 kgf / cm or more, more preferably 0.45 kgf / cm or more, even more preferably 0.50 kgf / cm or more, and particularly preferably 0.55 kgf / cm or more or 0.60 kgf / cm or more. The upper limit is not particularly limited, but it can be 10 kgf / cm or less, 1 kgf / cm or less, etc.

[0185] In one embodiment, the cured product of the resin composition of the present invention exhibits excellent crack resistance. For example, when the insulating layer (cured product) is subjected to desmear treatment as described in <Evaluation Example 4: Crack Resistance Evaluation Test> below, the percentage of cracks in the cured coating film (insulating layer after wet desmear treatment) is preferably less than 10%, more preferably less than 5%.

[0186] In one embodiment, the cured product of the resin composition according to the present invention exhibits excellent smear removal properties. For example, as described in the section "<Evaluation Example 5: Evaluation Test of Smear Removal Properties>" below, when a via hole is formed in the cured product and desmear treatment is performed, the length of the longest smear extending from the wall surface at the bottom of the via hole is preferably less than 5 μm, more preferably less than 3 μm.

[0187] As described above, the resin composition of the present invention can produce a cured product that simultaneously achieves excellent dielectric properties (low dielectric loss tangent), a low coefficient of linear thermal expansion, and excellent crack resistance. Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of printed wiring board), and more suitably used as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for interlayer insulating layer of printed wiring board). The resin composition of the present invention can also be suitably used when the printed wiring board is a circuit board with embedded components. The resin composition of the present invention can also be suitably used as a resin composition for forming an insulating layer of a redistribution substrate for a semiconductor package (resin composition for insulating layer of redistribution substrate). In this invention, printed wiring boards and redistribution substrates are collectively referred to as "circuit boards," and therefore the resin composition of the present invention can be suitably used for the insulating layer of a circuit board.

[0188] The resin composition of the present invention can be used in a wide range of applications where a resin composition is required, such as sheet-like laminated materials like resin sheets and prepregs, solder resists, underfill materials, die bonding materials, hole-filling resins, sealing resins, and component embedding resins.

[0189] [Sheet-like laminated materials (resin sheets, prepregs)] The resin composition of the present invention can be used as is, or it may be used in the form of a sheet-like laminated material containing the resin composition.

[0190] As sheet-like laminated materials, the following resin sheets and prepregs are preferred.

[0191] In one embodiment, the resin sheet comprises a support and a layer of a resin composition provided on the support (hereinafter simply referred to as the "resin composition layer"), wherein the resin composition layer is formed from the resin composition of the present invention.

[0192] The optimal thickness of the resin composition layer varies depending on the application and may be determined appropriately according to the application. For example, from the viewpoint of thinning printed circuit boards and semiconductor packages, the thickness of the resin composition layer is preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 1 μm or more, 5 μm or more, etc.

[0193] Examples of support materials include thermoplastic resin films, metal foils, and release paper, with thermoplastic resin films and metal foils being preferred. Therefore, in one preferred embodiment, the support material is a thermoplastic resin film or a metal foil.

[0194] When using a thermoplastic resin film as a support, examples of thermoplastic resins include polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); polycarbonate (PC); acrylic resins such as polymethyl methacrylate (PMMA); cyclic polyolefins; triacetylcellulose (TAC); polyether sulfide (PES); polyether ketones; and polyimides. Among these, polyester resins are preferred, polyethylene terephthalate or polyethylene naphthalate are more preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0195] When using a metal foil as a support, examples of metal foils include copper foil and aluminum foil, with copper foil being preferred. As for the copper foil, a foil containing a single metal of copper may be used, or a foil containing an alloy of copper with another metal (for example, tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used. In one embodiment, as the copper foil, a foil made of a single metal of copper may be used, or a foil made of an alloy of copper with another metal (for example, tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0196] The support may have a matte finish, corona treatment, or antistatic treatment applied to the surface that bonds with the resin composition layer. Alternatively, a support with a release layer may be used, which has a release layer on the surface that bonds with the resin composition layer. Examples of release agents used in the release layer of the support with a release layer include one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. Examples of commercially available release agents include "SK-1", "AL-5", and "AL-7" from Lintec Corporation. Furthermore, commercially available support with a release layer may also be used, for example, "Purex" from Toyobo Co., Ltd. and "Unipeel" from Unitika Corporation, which are PET films having a release layer mainly composed of alkyd resin-based release agents or polyolefin resin-based release agents.

[0197] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When using a support with a release layer, it is preferable that the overall thickness of the support with the release layer is within the above range.

[0198] When using metal foil as a support, a metal foil with a support substrate, which is formed by laminating a peelable support substrate onto a thin metal foil, may be used. In one embodiment, the metal foil with a support substrate includes a support substrate, a release layer provided on the support substrate, and a metal foil provided on the release layer. When using metal foil with a support substrate as a support, the resin composition layer is provided on the metal foil.

[0199] In a metal foil with a support substrate, the material of the support substrate is not particularly limited, but examples include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the support substrate, it may be electrolytic copper foil or rolled copper foil. Furthermore, the release layer is not particularly limited as long as it can be used to peel the metal foil from the support substrate, and examples include an alloy layer of elements selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, etc.

[0200] In a metal foil with a support substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.

[0201] In a metal foil with a support substrate, the thickness of the support substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, and more preferably in the range of 10 μm to 100 μm. The thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.

[0202] In one embodiment, the resin sheet may further include any additional layer as needed. Such an additional layer may be, for example, a protective film provided on the side of the resin composition layer that is not bonded to the support (i.e., the side opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 75 μm, preferably 1 μm to 40 μm. By laminating the protective film, the adhesion of dust and other debris to the surface of the resin composition layer and scratches can be suppressed.

[0203] Resin sheets can be manufactured, for example, by applying a resin varnish prepared by directly using a liquid resin composition or by dissolving the resin composition in an organic solvent, coating it onto a support using a die coater or the like, and then drying it to form a resin composition layer.

[0204] Examples of organic solvents include those similar to those described as components of the resin composition. Organic solvents may be used individually or in combination of two or more.

[0205] Drying may be carried out by known methods such as heating or blowing hot air. The drying conditions are not particularly limited, but the resin composition layer should be dried so that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. Depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, when using a resin composition or resin varnish containing 30% to 60% by mass of organic solvent, the resin composition layer can be formed by drying at 50°C to 150°C for 3 to 10 minutes.

[0206] Resin sheets can be stored by rolling them up. If the resin sheet has a protective film, it can be used after removing the protective film.

[0207] In one embodiment, the prepreg is formed by impregnating a sheet-like fibrous substrate with the resin composition of the present invention.

[0208] The sheet-like fibrous substrate used in the prepreg is not particularly limited, and commonly used prepreg substrates such as glass cloth, aramid nonwoven fabric, and liquid crystal polymer nonwoven fabric can be used. From the viewpoint of thinning printed circuit boards and semiconductor packages, the thickness of the sheet-like fibrous substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fibrous substrate is not particularly limited, but is usually 10 μm or more.

[0209] Prepregs can be manufactured by known methods such as the hot melt method and the solvent method.

[0210] The thickness of the prepreg can be within the same range as the resin composition layer in the resin sheet described above.

[0211] The sheet-like laminated material of the present invention can be suitably used to form an insulating layer of a printed circuit board (for the insulating layer of a printed circuit board), and more suitably used to form an interlayer insulating layer of a printed circuit board (for the interlayer insulating layer of a printed circuit board). The sheet-like laminated material of the present invention can also be suitably used to form an insulating layer of a redistribution substrate for a semiconductor package (for the insulating layer of a redistribution substrate). In other words, the sheet-like laminated material of the present invention can be suitably used as an insulating layer for a circuit board.

[0212] [Circuit board] An insulating layer of a circuit board can be formed using the resin composition of the present invention. The present invention also provides such a circuit board, that is, a circuit board including an insulating layer having a cured product of the resin composition of the present invention. In one embodiment, it is preferable that the circuit board of the present invention is a circuit board including an insulating layer made of a cured product of the resin composition of the present invention.

[0213] <Printed wiring board> In one embodiment, the circuit board of the present invention is a printed wiring board.

[0214] Printed circuit boards can be manufactured, for example, using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A process of laminating a resin sheet onto an inner layer substrate such that the resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing (e.g., thermal curing) the resin composition layer to form an insulating layer.

[0215] The "internal layer substrate" used in process (I) is a material that serves as the substrate for a printed wiring board, and examples include glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, thermosetting polyphenylene ether substrates, etc. The substrate may also have a conductive layer on one or both sides, and this conductive layer may be patterned. An internal layer substrate in which a conductive layer (circuit) is formed on one or both sides of the substrate is sometimes called an "internal layer circuit board." Furthermore, an intermediate product on which an insulating layer and / or a conductive layer is to be formed during the manufacturing of a printed wiring board is also included in the "internal layer substrate" as defined in this invention. If the printed wiring board is a circuit board with embedded components, an internal layer substrate with embedded components may be used.

[0216] The lamination of the inner layer substrate and the resin sheet can be performed, for example, by heating and pressing the resin sheet onto the inner layer substrate from the support side. Examples of the heating and pressing member used to heat and press the resin sheet onto the inner layer substrate (hereinafter also referred to as the "heat pressing member") include a heated metal plate (such as a SUS end plate) or a metal roll (such as a SUS roll). The heating and pressing member may be pressed directly onto the resin sheet, or it may be pressed via an elastic material such as heat-resistant rubber so that the resin sheet can adequately follow the surface irregularities of the inner layer substrate.

[0217] Lamination of the inner layer substrate and the resin sheet may be carried out by a vacuum lamination method. In the vacuum lamination method, the heat-pressure temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heat-pressure pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably in the range of 0.29 MPa to 1.47 MPa, and the heat-pressure time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. Lamination may preferably be carried out under reduced pressure conditions of 26.7 hPa or less.

[0218] Lamination can be performed using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include vacuum pressure laminators manufactured by Meiki Seisakusho Co., Ltd., vacuum applicators manufactured by Nikko Materials Co., Ltd., and batch-type vacuum pressure laminators.

[0219] After lamination, the laminated resin sheets may be smoothed by pressing a heat-sealing member from the support side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing process can be the same as the heat-sealing conditions for lamination. The smoothing process can be performed using a commercially available laminator. Lamination and smoothing may be performed continuously using the commercially available vacuum laminator mentioned above.

[0220] The support may be removed between steps (I) and (II), or after step (II). If a metal foil is used as the support, the conductive layer may be formed using the metal foil without peeling off the support. If a metal foil with a support substrate is used as the support, the support substrate (and release layer) should be peeled off. Then, the conductive layer can be formed using the metal foil.

[0221] In step (II), the resin composition layer is cured (e.g., by thermal curing) to form an insulating layer having a cured resin composition. In one embodiment, it is preferable in step (II) to cure (e.g., by thermal curing) the resin composition layer to form an insulating layer consisting of a cured resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions commonly used when forming an insulating layer of a printed circuit board may be used.

[0222] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, but in one embodiment, the curing temperature is preferably 140°C to 250°C, more preferably 150°C to 240°C, and even more preferably 180°C to 230°C. The curing time can be preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and even more preferably 15 minutes to 120 minutes.

[0223] Prior to thermal curing the resin composition layer, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermal curing the resin composition layer, it may be preheated at a temperature of 50°C to 140°C, preferably 60°C to 135°C, more preferably 70°C to 130°C for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0224] In manufacturing printed circuit boards, the following steps may be further performed: (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming the conductor layer. These steps (III) through (V) may be carried out according to various methods known to those skilled in the art that are used in the manufacture of printed circuit boards. If the support is removed after step (II), the removal of the support may be carried out between steps (II) and (III), between steps (III) and (IV), or between steps (IV) and (V). Furthermore, if necessary, the formation of the insulating layer and the conductor layer in steps (I) through (V) may be repeated to form a multilayer circuit board.

[0225] In other embodiments, the printed circuit board of the present invention can be manufactured using the prepreg described above. The manufacturing method is basically the same as when a resin sheet is used.

[0226] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as via holes and through holes in the insulating layer. Step (III) may be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined according to the design of the printed circuit board.

[0227] Step (IV) is a process for roughening the insulating layer. Typically, smear removal (desmear) is also performed in this step (IV). The procedure and conditions for the roughening process are not particularly limited, and known procedures and conditions commonly used when forming the insulating layer of a printed circuit board can be adopted. For example, the insulating layer can be roughened by performing swelling treatment with a swelling solution, roughening treatment with an oxidizing agent, and neutralization treatment with a neutralizing solution in this order.

[0228] The swelling solution used for the roughening treatment is not particularly limited, but examples include alkaline solutions and surfactant solutions, and is preferably an alkaline solution, with sodium hydroxide solution and potassium hydroxide solution being more preferred. Examples of commercially available swelling solutions include "Swelling Dip Securing P" and "Swelling Dip Securing SBU" manufactured by Atotec Japan. The swelling treatment with the swelling solution is not particularly limited, but can be carried out, for example, by immersing the insulating layer in a swelling solution at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling solution at 40°C to 80°C for 5 to 15 minutes.

[0229] The oxidizing agent used for the roughening treatment is not particularly limited, but examples include an alkaline permanganate solution obtained by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide. The roughening treatment with an oxidizing agent such as an alkaline permanganate solution is preferably carried out by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 to 30 minutes. Furthermore, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Attec Japan.

[0230] Furthermore, an acidic aqueous solution is preferred as the neutralizing solution used in the roughening treatment. A commercially available example is "Reduction Solution Securigant P" manufactured by Attec Japan.

[0231] The neutralization treatment can be carried out by immersing the treated surface, which has been roughened with an oxidizing agent, in a neutralization solution at 30°C to 80°C for 5 to 30 minutes. From the standpoint of workability, it is preferable to immerse the object, which has been roughened with an oxidizing agent, in a neutralization solution at 40°C to 70°C for 5 to 20 minutes.

[0232] Step (V) is a step of forming a conductive layer, in which a conductive layer is formed on an insulating layer. The conductive material used for the conductive layer is not particularly limited. In a preferred embodiment, the conductive layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductive layer may be a single-metal layer or an alloy layer, and examples of alloy layers include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). In particular, from the viewpoint of versatility in conductor layer formation, cost, and ease of patterning, single metal layers of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or alloy layers of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy are preferred, single metal layers of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or alloy layers of nickel-chromium alloy are more preferred, and single metal layers of copper are even more preferred.

[0233] The conductive layer may be a single layer or a multilayer structure in which two or more single-metal layers or alloy layers containing different types of metals or alloys are laminated. In one embodiment, the conductive layer may be a single layer or a multilayer structure in which two or more single-metal layers or alloy layers made of different types of metals or alloys are laminated. When the conductive layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single-metal layer of chromium, zinc, or titanium, or an alloy layer of nickel-chromium alloy.

[0234] The thickness of the conductor layer depends on the desired design of the printed wiring board, and is generally from 3 μm to 35 μm, preferably from 5 μm to 30 μm.

[0235] In one embodiment, the conductor layer may be formed by plating. From the viewpoint of facilitating formation of fine wiring, it is preferably formed by a semi-additive method. Hereinafter, an example of forming the conductor layer by the semi-additive method is described.

[0236] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern that exposes a part of the plating seed layer corresponding to a desired wiring pattern is formed on the formed plating seed layer. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, the unnecessary plating seed layer can be removed by etching or the like, to form a conductor layer having a desired wiring pattern.

[0237] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, Step (V) is preferably performed between Step (I) and Step (II). For example, after Step (I), the support is removed, and the metal foil is laminated on the exposed surface of the resin composition layer. Lamination of the resin composition layer and the metal foil may be performed by a vacuum lamination method. The lamination conditions may be the same as the conditions described for Step (I). Next, Step (II) is performed to form an insulating layer. Thereafter, by using the metal foil on the insulating layer, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a modified semi-additive method.

[0238] The metal foil can be produced by a known method such as an electrolytic method and a rolling method. Examples of commercially available products of the metal foil include HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd., and the like.

[0239] Alternatively, as mentioned above, if a metal foil or a metal foil with a support substrate is used as the support for the resin sheet, the conductive layer may be formed using the metal foil.

[0240] <Semiconductor package redistribution substrate> In one embodiment, the circuit board of the present invention is a redistribution substrate (redistribution layer) for a semiconductor package. The following description will be based on the manufacturing method of the semiconductor package.

[0241] The semiconductor package includes an insulating layer having a cured product of the resin composition of the present invention as an insulating layer of the redistribution substrate. In one embodiment, it is preferable that the semiconductor package includes an insulating layer made of a cured product of the resin composition of the present invention as an insulating layer of the redistribution substrate. The semiconductor package may also include a sealing layer having a cured product of the resin composition of the present invention. In one embodiment, the semiconductor package may include a sealing layer made of a cured product of the resin composition of the present invention.

[0242] A semiconductor package can be manufactured, for example, using the resin composition and resin sheet of the present invention by a method including the following steps (1) to (6). The resin composition and resin sheet of the present invention may be used to form the redistribution layer (insulating layer for forming a redistribution substrate) in step (5) or the sealing layer in step (3). An example of forming a redistribution layer and a sealing layer using the resin composition and resin sheet is shown below, but the techniques for forming redistribution layers and sealing layers of semiconductor packages are well known, and those skilled in the art can manufacture semiconductor packages using the resin composition and resin sheet of the present invention in accordance with known techniques. (1) A step of laminating a temporary fixing film onto the substrate, (2) A step of temporarily fixing the semiconductor chip onto a temporary fixing film, (3) A step of forming a sealing layer on a semiconductor chip, (4) Steps to peel off the substrate and temporary fixing film from the semiconductor chip, (5) A step of forming a rewiring layer as an insulating layer on the surface from which the substrate and temporary fixing film of the semiconductor chip have been peeled off, and (6) Step of forming a redistribution layer as a conductor layer on the redistribution formation layer.

[0243] <<Process (1)>> The material used for the substrate is not particularly limited. Examples of substrates include semiconductor wafers such as silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC); substrates made by impregnating glass fibers with epoxy resin and heat-curing treatment (e.g., FR-4 substrates); and bismaleimidotriazine resin (BT resin) substrates. In one embodiment, the bismaleimidotriazine resin (BT resin) substrate is a substrate made of bismaleimidotriazine resin (BT resin).

[0244] The temporary fixing film is not limited in material as long as it can be peeled off from the semiconductor chip in step (4) and temporarily fix the semiconductor chip. Commercially available temporary fixing films can be used. Examples of commercially available products include Riva Alpha manufactured by Nitto Denko Corporation.

[0245] <<Process (2)>> Temporary fixing of semiconductor chips can be performed using known devices such as flip-chip bonders and die bonders. The layout and number of semiconductor chips can be appropriately set according to the shape and size of the temporary fixing film, the number of semiconductor packages to be produced, etc. For example, they can be temporarily fixed in a matrix arrangement with multiple rows and multiple columns.

[0246] <<Process (3)>> The resin composition layer of the resin sheet of the present invention is laminated onto a semiconductor chip, or the resin composition of the present invention is applied onto a semiconductor chip and cured (e.g., by heat curing) to form a sealing layer.

[0247] For example, lamination of a semiconductor chip and a resin sheet can be performed by removing the protective film from the resin sheet and then heating and pressing the resin sheet onto the semiconductor chip from the support side. Examples of the heating and pressing member used to heat and press the resin sheet onto the semiconductor chip (hereinafter also referred to as the "heating and pressing member") include a heated metal plate (such as a SUS end plate) or a metal roll (such as a SUS roll). It is preferable to press the resin sheet via an elastic material such as heat-resistant rubber, rather than directly pressing the heating and pressing member onto the resin sheet, so that the resin sheet can adequately follow the surface irregularities of the semiconductor chip. Lamination of the semiconductor chip and the resin sheet may also be carried out by a vacuum lamination method, and the lamination conditions are the same as those described in relation to the manufacturing method of printed circuit boards, and the preferred range is also the same.

[0248] After lamination, the resin composition is heat-cured to form a sealing layer. The heat-curing conditions are the same as those described in relation to the manufacturing method of printed circuit boards.

[0249] The resin sheet support may be peeled off after the resin sheet has been laminated onto the semiconductor chip and heat-cured, or the support may be peeled off before the resin sheet has been laminated onto the semiconductor chip.

[0250] When applying the resin composition of the present invention to form a sealing layer, the application conditions are the same as those for forming the resin composition layer described in relation to the resin sheet of the present invention, and the preferred ranges are also the same.

[0251] <<Process (4)>> The method for peeling off the substrate and the temporary fixing film can be appropriately changed depending on the material of the temporary fixing film, etc. Examples include a method of peeling off the temporary fixing film by heating and foaming (or expanding) it, and a method of peeling off the temporary fixing film by irradiating it with ultraviolet light from the substrate side to reduce the adhesive strength of the temporary fixing film.

[0252] In the method of peeling the temporarily fixed film by heating and foaming (or expanding) it, the heating conditions are usually 100 to 250°C for 1 to 90 seconds or 5 to 15 minutes. Further, in the method of peeling by irradiating ultraviolet rays from the base material side to reduce the adhesive force of the temporarily fixed film, the irradiation dose of ultraviolet rays is usually 10 mJ / cm 2 ~1000mJ / cm 2 .

[0253] <<Step (5)>> Using the resin composition and resin sheet of the present invention, a rewiring forming layer (the insulating layer of the rewiring substrate) is formed.

[0254] After forming the rewiring forming layer, via holes may be formed in the rewiring forming layer for interlayer connection between the semiconductor chip and the conductor layer described later. The via holes may be formed by a known method according to the material of the rewiring forming layer.

[0255] <<Step (6)>> The formation of the conductor layer on the rewiring forming layer may be carried out in the same manner as step (V) described in relation to the method for manufacturing a printed wiring board. Note that step (5) and step (6) may be repeated to alternately stack (build up) the conductor layer (rewiring layer) and the rewiring forming layer (insulating layer).

[0256] In manufacturing a semiconductor package, the following steps may be further carried out: (7) a step of forming a solder resist layer on the conductor layer (rewiring layer), (8) a step of forming bumps, and (9) a step of dicing a plurality of semiconductor packages into individual semiconductor packages to separate them into individual pieces. These steps may be carried out according to various methods known to those skilled in the art that are used in the manufacture of semiconductor packages.

[0257] The resin composition and resin sheet of the present invention, which can produce a cured product exhibiting low dielectric loss tangent, excellent smear removal properties, and high heat resistance (glass transition temperature), can be used to form a redistribution layer (insulating layer) to realize a semiconductor package with extremely low transmission loss, regardless of whether it is a fan-in or fan-out type package, without concerns about cracks or circuit distortion. In one embodiment, the semiconductor package of the present invention is a fan-out type package. The resin composition and resin sheet of the present invention can be applied to fan-out type panel-level packages (FOPLPs) and fan-out type wafer-level packages (FOWLPs). In one embodiment, the semiconductor package of the present invention is a fan-out type panel-level package (FOPLP) or a fan-out type wafer-level package (FOWLP).

[0258] [Semiconductor device] The semiconductor device of the present invention includes an insulating layer having a cured product of the resin composition of the present invention. In one embodiment, it is preferable that the semiconductor device of the present invention includes an insulating layer made of a cured product of the resin composition of the present invention. That is, the semiconductor device of the present invention includes a circuit board of the present invention. The semiconductor device of the present invention can be manufactured using the circuit board of the present invention.

[0259] Examples of semiconductor devices include various types of semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, and televisions) and vehicles (e.g., motorcycles, automobiles, trains, ships, and aircraft). [Examples]

[0260] The present invention will be described in detail below with reference to examples. The present invention is not limited to these examples. In the following, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "% by mass," respectively.

[0261] <Synthesis Example 1: Synthesis of Active Ester Resin (B-1)> In a flask equipped with a thermometer, dropping funnel, condenser, fractionation column, and stirrer, 320 g (2.0 mol) of 2,7-dihydroxynaphthalene, 184 g (1.7 mol) of benzyl alcohol, and 5.0 g of p-toluenesulfonic acid monohydrate were charged and stirred at room temperature while blowing in nitrogen. Then, the temperature was raised to 150°C and the mixture was stirred for 4 hours while distilling off the water produced. After the reaction was complete, 900 g of methyl isobutyl ketone and 5.4 g of 20% sodium hydroxide aqueous solution were added to neutralize the mixture. The aqueous layer was then removed by liquid-liquid extraction, and the organic layer was washed three times with 280 g of water. Methyl isobutyl ketone was removed from the resulting organic layer under reduced pressure to obtain 460 g of benzyl-modified naphthalene compound (B-1'). The obtained benzyl-modified naphthalene compound (B-1') was a black solid with a hydroxyl group equivalent of 180 g / eq.

[0262] In a flask equipped with a thermometer, dropping funnel, condenser, fractionation column, and stirrer, 203.0 g of isophthalic acid chloride (2.0 moles of acid chloride groups) and 1400 g of toluene were charged, and the system was dissolved under reduced pressure and nitrogen purging. Next, 113.9 g (0.67 moles) of orthophenylphenol and 240 g of benzyl-modified naphthalene compound (B-1') (1.33 moles of phenolic hydroxyl groups) were charged, and the system was dissolved under reduced pressure and nitrogen purging. Subsequently, 0.70 g of tetrabutylammonium bromide was dissolved, and while purging with nitrogen gas, the system temperature was controlled to below 60°C, and 400 g of 20% sodium hydroxide aqueous solution was added dropwise over 3 hours. Stirring was then continued under these conditions for 1.0 hour. After the reaction was complete, the mixture was allowed to stand and separated, and the aqueous layer was removed. Furthermore, water was added to the toluene layer in which the product was dissolved, and the mixture was stirred for 15 minutes. The aqueous layer was then removed by standing liquid-liquid extraction. This procedure was repeated until the pH of the aqueous layer reached 7. Subsequently, water was removed by decanting to obtain the activated ester resin (B-1) in a toluene solution with 62% by mass of nonvolatile components. The active ester equivalent of the obtained activated ester resin (B-1) was 238 g / eq.

[0263] [ka]

[0264] <Synthesis Example 2: Synthesis of Maleimide Resin (C-1)> According to Synthesis Example 1 in the Japan Institute of Invention and Innovation Published Technical Report No. 2020-500211, a MEK solution (62% by mass of non-volatile components) of maleimide resin (C-1) represented by the following formula (C-1) was prepared. The Mw / Mn of this maleimide resin (C-1) was 1.81, and t'' in formula (C-1) was 1.47 (mainly 1, 2, or 3).

[0265] [ka]

[0266] <Synthesis Example 3: Synthesis of Maleimide Resin (C-2)> (I) Synthesis of intermediate amine compound (c) In a flask equipped with a thermometer, condenser, Dean-Stark trap, and stirrer, 400 g (3.3 mol) of 2-ethylaniline, 127 g of compound (b) having a benzyl ether skeleton (Nikanol L, manufactured by Fudo Co., Ltd.), 193 g of toluene, and 53 g of activated clay were charged. The mixture was heated to 120°C while stirring and held for 30 minutes. Then, the temperature was raised to 150°C and held for 3 hours. After holding, the temperature was raised to 200°C over 30 minutes and held for 10 hours. After holding, the mixture was diluted with 193 g of toluene, and the activated clay was filtered off. From the filtrate, the solvent and excess 2-ethylaniline were removed by heating and reduced pressure to obtain the intermediate amine compound (c) (amine equivalent 209 g / eq.).

[0267] (II) Maleimidization A 2L flask equipped with a thermometer, condenser, Dean-Stark trap, and stirrer was charged with 73.2g (126mol, 1.3 equivalents) of maleic anhydride and 461g of toluene, and stirred at room temperature. Next, a mixed solution of intermediate amine compound (c) 209g (1 equivalent) and N,N-dimethylformamide (DMF) 57.7g was added dropwise over 1 hour, and the reaction was allowed to proceed for 2 hours. 9.72g of p-toluenesulfonic acid monohydrate was added to the reaction solution, and the solution was heated to 115°C. The azeotropic water and toluene were cooled and separated under reflux, and only toluene was returned to the system for dehydration for 5 hours. After air cooling to room temperature, the brown solution obtained by concentration under reduced pressure was dissolved in 600g of ethyl acetate and washed three times with 200g of deionized water and three times with 150g of 2% by mass sodium bicarbonate aqueous solution. After adding sodium sulfate and drying, the product was concentrated under reduced pressure and vacuum-dried at 80°C for 4 hours to obtain maleimide resin (C-2). Maleimide resin (C-2) mainly contained a maleimide compound represented by the following formula (C-2). In formula (C-2), n represents an integer of 1 or more, and n 1 Each of these independently represents the number of repeating units, and Et represents the ethyl group.

[0268] [ka]

[0269] <Examples 1-29 and Comparative Examples 30-39> (1) Manufacturing of resin composition Each component was weighed and mixed according to the formulations described in Tables 1 to 4 below, and then 10 parts of MEK (methyl ethyl ketone) and 10 parts of cyclohexanone were added and uniformly dispersed using a high-speed rotary mixer to obtain a resin composition (resin varnish).

[0270] [Table 1]

[0271] [Table 2]

[0272] [Table 3]

[0273] [Table 4]

[0274] Furthermore, the details of each component listed in Tables 1-4 are as follows: (A) Epoxy resin • NC-3000L: Epoxy equivalent 271g / eq., manufactured by Nippon Kayaku Co., Ltd., biphenyl-type epoxy resin HP-4032SS: Epoxy equivalent 144g / eq., manufactured by DIC Corporation, naphthalene-type epoxy resin

[0275] (B) Active ester resin • HPC-8000L-65MT: Active ester equivalent 220 g / eq., manufactured by DIC Corporation, active ester resin containing a dicyclopentadiene-type diphenol structure, mixed solution of MEK and toluene with 65% non-volatile components. • Activated ester resin (B-1): Activated ester resin (B-1) obtained in Synthesis Example 1, 238 g / eq. of activated ester equivalent, toluene solution with 62% non-volatile components. • Activated ester resin (B-2): Activated ester resin (B-2) represented by the following formula (mainly composed of compounds where n is an integer from 0 to 6), 250 g / eq. of activated ester equivalent, toluene solution with 60% non-volatile components.

[0276] [ka]

[0277] • Activated ester resin (B-3): Activated ester resin (B-3) represented by the following formula (mainly composed of compounds where n is an integer from 0 to 6), 249 g / eq. of activated ester equivalent, toluene solution with 65% non-volatile components.

[0278] [ka]

[0279] (C1) Maleimide resin having an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less. • Maleimide resin (C-1): Maleimide resin (C-1) obtained in Synthesis Example 2, in a toluene solution with 62% non-volatile components. • Maleimide resin (C-2): Maleimide resin (C-2) obtained in Synthesis Example 3, in a toluene solution with 62% non-volatile components. • MIR-5000-60T: Maleimide resin represented by the following formula, manufactured by Nippon Kayaku Co., Ltd., toluene solution with 60% non-volatile components.

[0280] [ka]

[0281] • Maleimide resin (C-4): Maleimide resin represented by the following formula (C-4) (wherein X is a divalent group represented independently by one of the following formulas (a') to (d'), where m≧0 and n≧1. In formulas (a') to (d'), * represents a bond to the nitrogen atom of the maleimide group, and m, n, p, and q are integers of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, respectively. Bonds shown by dashed lines represent carbon-carbon single bonds or carbon-carbon double bonds. However, if a bond shown by a dashed line is a carbon-carbon double bond, the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is one less than the number shown in formulas (a') to (d').)

[0282] [ka]

[0283] (C2) Maleimide resins that do not have aromatic rings, or have aromatic rings, but the ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) is greater than 0.25. • BMI-689: An N-alkylbismaleimide manufactured by Designer Molecules Inc., having a skeleton derived from a dimeramine with the structure represented by the following formula (C2-2).

[0284] [ka]

[0285] • SLK-1500-T80: A toluene solution containing 80% non-volatile components, containing an N-alkylbismaleimide having a skeleton derived from a dimeramine with the structure represented by the following formula (C2-1), manufactured by Shin-Etsu Chemical Co., Ltd.

[0286] [ka] (In equation (C2-1), the mean value of n is 1.3.)

[0287] (D) Inorganic filler • SO-C2: Spherical silica manufactured by Admatex, with an average particle size of 0.5 μm, surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573," N-phenyl-3-aminopropyltrimethoxysilane). • LHP-208: Hollow silica manufactured by Ube Eximo Co., Ltd., with an average particle size of 0.5 μm, porosity of 50% by volume, and surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573", N-phenyl-3-aminopropyltrimethoxysilane). • MGH-005: Hollow silica manufactured by Taiheiyo Cement Corporation, with an average particle size of 1.6 μm, porosity of 80% by volume, and surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573," N-phenyl-3-aminopropyltrimethoxysilane).

[0288] (E) Organic filler • EXL-2655: A core-shell type cushion filler containing rubber components, manufactured by Dow Corporation.

[0289] (F)Thermoplastic resin • YX7553BH30: A phenoxy resin mixed solution containing 30% non-volatile MEK and cyclohexanone, manufactured by Mitsubishi Chemical Corporation.

[0290] (G) Curing accelerator • 1B2PZ: Imidazole-based curing accelerator (1-benzyl-2-phenylimidazole), manufactured by Shikoku Chemicals Co., Ltd. • BT-120: Triazole-based curing accelerator (1,2,3-benzotriazole), manufactured by Johoku Chemical Industry Co., Ltd.

[0291] (1) Preparation of evaluation film A glass cloth-based epoxy resin double-sided copper-clad laminate (Panasonic R5715ES, 0.7 mm thick, 255 mm square) was placed on the untreated side of a PET film (50 μm thick, 240 mm square) treated with Lintec's "1010" release agent, and the four sides were fixed with polyimide adhesive tape (10 mm wide) (hereinafter sometimes referred to as "fixed PET film").

[0292] The resin compositions obtained in the examples and comparative examples were applied to the release-treated surface of the "fixed PET film" using an applicator so that the thickness of the dried resin composition layer was 40 μm, and dried at 90°C for 3 minutes. Resin sheet A, consisting of a PET film and a resin composition layer, was obtained by removing it from the glass cloth substrate epoxy resin double-sided copper-clad laminate. Resin sheet B was obtained by the same manufacturing method as resin sheet A, except that the coating thickness of the resin composition was changed so that the thickness of the dried resin composition layer was 27.5 μm.

[0293] (2) Preparation of hardened material for evaluation Resin sheet A was placed in an oven at 190°C and the resin composition layer was heat-cured for 90 minutes under curing conditions. After heat curing, the PET film was peeled off to obtain a sheet-like cured product. The obtained cured product is referred to as the "evaluation cured product".

[0294] <Evaluation Example 1: Measurement of Dielectric Loss Tangent> The cured material for evaluation was cut to obtain test specimens measuring 50 mm in width and 50 mm in length. The dielectric loss tangent Df of these specimens was measured using the Fabry-Perot resonator method with a Keysight Technologies N5227B network analyzer at a measurement frequency of 150 GHz and a measurement temperature of 90°C. Measurements were performed on two specimens, the average value was calculated, and the results were evaluated according to the following criteria. "◎": Dielectric loss tangent is less than 0.0045 "○": Dielectric loss tangent is 0.0045 or greater and less than 0.0050 "×": Dielectric loss tangent is 0.0050 or higher

[0295] <Evaluation Example 2: Measurement of Linear Thermal Expansion Coefficient (CTE)> The cured material for evaluation was cut into pieces 20 mm long and 6 mm wide to obtain cured material samples for measuring the coefficient of linear thermal expansion. These cured material samples were heated from 25°C to 220°C at a heating rate of 5°C / min using a TMA (thermomechanical analyzer, Rigaku Corporation) and measured. Subsequently, the same test piece was heated from 25°C to 220°C at a heating rate of 5°C / min and measured again. The coefficient of linear thermal expansion (CTE) was calculated from the results of the second measurement and evaluated according to the following criteria. "○": CTE is less than 25 ppm / ℃ "△": CTE is between 25 ppm / °C and 30 ppm / °C "×": CTE is 30 ppm / ℃ or higher

[0296] <Evaluation Example 3: Evaluation Test of Adhesion to Copper Substrate> (3-1) Lamination of resin sheet B onto inner layer substrate As an inner layer circuit board with copper foil on both sides, a glass cloth substrate epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") was prepared. The surfaces of the copper foil on both sides of the inner layer circuit board were roughened using MEC's ​​"CZ8101" (copper etching amount 1.0 μm).

[0297] Resin sheet B was laminated onto both sides of the inner circuit board using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd. 2-stage build-up laminator "CVP700") so that the resin composition layer of resin sheet B was bonded to the inner circuit board. Lamination was performed by reducing the pressure to 13 hPa or less for 30 seconds, followed by pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet B was heat-pressed at atmospheric pressure, 100°C, and a pressure of 0.5 MPa for 60 seconds to smooth it out. After that, the support film (PET film) was peeled off to obtain an "intermediate multilayer body I" containing the resin composition layer / inner circuit board / resin composition layer in that order.

[0298] (3-2) Lamination of copper foil A copper foil with a glossy surface (35 μm thick, manufactured by Mitsui Mining & Smelting Co., Ltd., "3EC-III") was prepared. The glossy surface of this copper foil was roughened by etching with a micro-etching agent (manufactured by MEC Corporation, "CZ8401") to a copper etching depth of 0.1 μm. The copper foil obtained in this way is called "roughened copper foil".

[0299] This roughened copper foil was laminated on both sides of the intermediate multilayer I such that the roughened surface of the roughened copper foil was bonded to the resin composition layer of the intermediate multilayer I. This lamination was carried out under the same conditions as the lamination of resin sheet B to the inner substrate described above. As a result, an "intermediate multilayer II" was obtained, containing roughened copper foil / resin composition layer / inner substrate / resin composition layer / roughened copper foil in this order.

[0300] (3-3) Thermocuring of the resin composition layer The obtained intermediate multilayer II was placed in a 130°C oven and heated for 30 minutes, then transferred to a 170°C oven and heated for another 30 minutes. Next, the intermediate multilayer II was removed from the oven and left in a room temperature atmosphere, and then placed in a 190°C oven and heated for an additional 90 minutes. This caused the resin composition layer to heat-cur, yielding "evaluation substrate A" containing, in this order, roughened copper foil / insulating layer as a cured product of the resin composition layer / inner layer substrate / insulating layer as a cured product of the resin composition layer / roughened copper foil. In evaluation substrate A, the roughened copper foil corresponds to the conductive layer.

[0301] (3-4) Measurement of adhesion strength with the conductor layer Using the obtained evaluation substrate A, the peel strength between the roughened copper foil and the insulating layer was measured. This peel strength measurement was performed in accordance with JIS C6481. Specifically, the peel strength was measured by the following procedure.

[0302] A rectangular section measuring 10 mm wide and 100 mm long was cut into the roughened copper foil of evaluation substrate A. One end of this rectangular section was peeled off and grasped with a gripper (TSE Corporation's Autocom type testing machine "AC-50C-SL"). A 35 mm length section of this rectangular area was peeled vertically, and the load (kgf / cm) during this peeling was measured as the peel strength. The above peeling was performed at a speed of 50 mm / min at room temperature.

[0303] A higher peel strength indicates better adhesion to the underlying copper. Therefore, the measured peel strength was evaluated based on the following criteria. "〇": Peel strength of 0.50 kgf / cm or higher "×": Peel strength is less than 0.50 kgf / cm

[0304] <Evaluation Example 4: Crack Resistance Evaluation Test> (4-1) Preparation of the inner layer substrate A glass cloth substrate epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") with an inner layer circuit formed on it was etched 1 μm on both sides with a micro-etching agent (MEC "CZ8101") to roughen the copper surface and obtain an inner layer substrate.

[0305] (4-2) Lamination of resin sheet B Using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd., 2-stage build-up laminator "CVP1700"), resin sheet B was laminated on both sides of the inner layer substrate so that the resin composition layer was in contact with the inner layer substrate. Lamination was performed by reducing the pressure to 13 hPa or less by depressurizing for 30 seconds, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Subsequently, the resin composition layer was smoothed by heat pressing at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0306] (4-3) Thermocuring of the resin composition layer Subsequently, the inner layer substrate with the resin sheet B laminated on it was placed in a 130°C oven and heated for 30 minutes, then transferred to a 170°C oven and heated for another 30 minutes to heat-cur the resin composition layer and form an insulating layer. After that, the support was peeled off to obtain a cured substrate X having an insulating layer / inner layer substrate / insulating layer structure.

[0307] (4-4) Roughening treatment The insulating layer of the obtained cured substrate X was subjected to a desmear treatment as a roughening treatment. The following wet desmear treatment was performed.

[0308] (Wet desmear treatment) The cured substrate X was immersed in a swelling solution (Atotec Japan's "Swelling Dip Securigant P," an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes. Next, the cured substrate was immersed in an oxidizing agent solution (Atotec Japan's "Concentrate Compact P," an aqueous solution with approximately 6% potassium permanganate and approximately 4% sodium hydroxide) at 80°C for 25 minutes. Finally, the cured substrate was immersed in a neutralizing solution (Atotec Japan's "Reduction Solution Securigant P," an aqueous sulfuric acid solution) at 40°C for 5 minutes. After that, the cured substrate was dried at 80°C for 15 minutes. This cured substrate after desmear treatment may hereafter be referred to as "evaluation substrate B."

[0309] (4-5) Evaluation of crack resistance In accordance with JIS K 5600-5-6, a grid pattern of cuts was made on evaluation substrate B, and the presence or absence of cracks in the cured coating (insulating layer after wet desmear treatment) was observed and evaluated using an optical microscope. Specifically, a grid pattern of cuts was made in the cured coating of evaluation substrate B at 1 mm intervals, forming 10 coating pieces in the vertical direction and 10 in the horizontal direction, for a total of 100 coating pieces. Here, a coating piece refers to each part of the cured coating partitioned by the cuts. These 100 coating pieces were observed with an optical microscope, and the number of coating pieces with cracks was counted. Based on the ratio of the number of coating pieces with cracks to the total number of coating pieces (100), crack resistance was evaluated according to the following evaluation criteria. (Evaluation Criteria) "○": The percentage of cracks in the cured coating film is less than 5%. "△": The percentage of cracks in the cured coating is 5% or more but less than 10%. "×": The percentage of cracks in the cured coating is 10% or more.

[0310] <Evaluation Example 5: Evaluation Test of Smear Removal Ability> (5-1) Preparation of the inner layer substrate A glass cloth substrate epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") with an inner layer circuit formed on it was etched 1 μm on both sides with a micro-etching agent (MEC "CZ8101") to roughen the copper surface and obtain an inner layer substrate.

[0311] (5-2) Lamination of resin sheet B Using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd., 2-stage build-up laminator "CVP1700"), resin sheet B was laminated on both sides of the inner layer substrate so that the resin composition layer was in contact with the inner layer substrate. Lamination was performed by reducing the pressure to 13 hPa or less by depressurizing for 30 seconds, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Subsequently, the resin composition layer was smoothed by heat pressing at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0312] (5-3) Thermocuring of the resin composition layer Subsequently, the inner layer substrate with the resin sheet B laminated on it was placed in a 130°C oven and heated for 30 minutes, then transferred to a 170°C oven and heated for another 30 minutes to heat-cur the resin composition layer and form an insulating layer. After that, the support (PET film) was peeled off to obtain a cured substrate Y having an insulating layer / inner layer substrate / insulating layer structure.

[0313] (5-4) Formation of a beer hall The insulating layer of the obtained cured substrate Y was drilled using a CO2 laser processing machine (LK-2K212 / 2C, manufactured by Via Mechanics Co., Ltd.) under the conditions of a frequency of 2000 Hz, a pulse width of 3 μs, an output of 0.95 W, and 3 shots, to form via holes. The opening diameter (top diameter) of the formed via holes on the insulating layer surface was 50 μm, and the diameter (bottom diameter) at the bottom of the insulating layer was 40 μm.

[0314] (5-5) Roughening treatment The insulating layer of the hardened substrate, which had via holes formed on it, was subjected to a desmear treatment as a roughening treatment. The following wet desmear treatment was performed.

[0315] (Wet desmear treatment) The cured substrate, with via holes formed on it, was immersed in a swelling solution (Atotec Japan's "Swelling Dip Securigant P," an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes. Next, the cured substrate was immersed in an oxidizing agent solution (Atotec Japan's "Concentrate Compact P," an aqueous solution of approximately 6% potassium permanganate and approximately 4% sodium hydroxide) at 80°C for 25 minutes. Finally, the cured substrate was immersed in a neutralizing solution (Atotec Japan's "Reduction Solution Securigant P," an aqueous sulfuric acid solution) at 40°C for 5 minutes. After that, the cured substrate was dried at 80°C for 15 minutes. This cured substrate after desmear treatment may hereafter be referred to as "evaluation substrate C."

[0316] (5-6) Evaluation of smear removal ability For evaluation substrate C, the area around the bottom of the via holes was observed using a scanning electron microscope (SEM). From the obtained images, the length of the longest smear (resin residue) extending from the wall surface at the bottom of the via holes (maximum smear length) was measured and evaluated according to the following criteria. "◎": Maximum smear length is less than 3 μm "〇": Maximum smear length is 3 μm or more and less than 5 μm. "×": Maximum smear length is 5 μm or more

[0317] <Test Example 6: Measurement of Elongation (Elongation at Breaking Point)> Tensile strength measurements were performed on the cured samples used for evaluation, employing an Orientec RTC-1250A tensile testing machine. The elongation at the breaking point at 23°C was measured. The measurements were conducted in accordance with JIS K7127. Five measurements were performed, and the average of the top three results was calculated. "◎": Elongation at break of 1.8% or more "〇": Elongation at break 1.5% or more and less than 1.8% "×": Breaking elongation less than 1.5%

[0318] As shown in Tables 1-4, in Examples 1-29, which contained (A) epoxy resin, (B) active ester resin, (C1) maleimide resin having aromatic rings and a ratio of dimeramine skeletons to aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and (C2) maleimide resin without aromatic rings, or having aromatic rings and a ratio of dimeramine skeletons to aromatic rings (dimeramine / aromatic ring) greater than 0.25, and where the ratio [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] was 1.3 or more, excellent dielectric loss tangent, low coefficient of linear thermal expansion, high elongation (high elongation at breaking point), and excellent crack resistance were achieved simultaneously. On the other hand, in Comparative Example 30, which did not contain maleimide resin, the elongation (elongation at breaking point) and crack resistance were not at a satisfactory level. In Comparative Examples 31-34, where the ratio [total number of moles of active groups in component (B) / total number of moles of active groups in component (A)] was less than 1.3, the dielectric loss tangent was not at a satisfactory level. When the ratio [total number of moles of active groups in component (B) / total number of moles of active groups in component (A)] was less than 1.3, although the linear thermal expansion coefficient, elongation (elongation at fracture), and crack resistance could be controlled by the presence or absence of components (C1) and (C2), it was not possible to simultaneously achieve excellent dielectric loss tangent, low linear thermal expansion coefficient, high elongation (high elongation at fracture), and excellent crack resistance. Furthermore, Comparative Example 35, which did not contain component (C2), did not have satisfactory levels of elongation (elongation at fracture) and crack resistance. Comparative Example 36, which did not contain component (C1), did not have a satisfactory level of linear thermal expansion coefficient. Comparative Example 37, which does not contain (B) activated ester resin, did not meet satisfactory levels of dielectric loss tangent, linear thermal expansion coefficient, elongation (elongation at break), and crack resistance. Comparative Example 38, which does not contain (B) activated ester resin and (C1) component, did not meet satisfactory levels of dielectric loss tangent and linear thermal expansion coefficient. Comparative Example 39, which does not contain (A) epoxy resin and (B) activated ester resin, did not meet satisfactory levels of linear thermal expansion coefficient, elongation (elongation at break), and crack resistance.

Claims

1. (A) Epoxy resin, (B) Active ester resin, and (C) Maleimide resin, A resin composition containing, (C) comprises a maleimide resin having an aromatic ring (C1) and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of 0.25 or less, and a maleimide resin having no aromatic ring or having an aromatic ring and a ratio of the number of dimeramine skeletons to the number of aromatic rings (dimeramine / aromatic ring) of more than 0.

25. A resin composition in which the ratio of the total number of moles of active groups of component (B) to the total number of moles of active groups of component (A) [total number of moles of active groups of component (B) / total number of moles of active groups of component (A)] is 1.3 or greater.

2. The resin composition according to claim 1, wherein the content of component (A) is 15 to 30% by mass when the total amount of resin components in the resin composition is 100% by mass.

3. The resin composition according to claim 1, wherein the content of component (B) is 10 to 70% by mass when the total amount of resin components in the resin composition is 100% by mass.

4. The resin composition according to claim 1, wherein the content of component (C1) is 1 to 30% by mass when the total amount of resin components in the resin composition is 100% by mass.

5. The resin composition according to claim 1, wherein the content of component (C2) is 1 to 20% by mass when the total amount of resin components in the resin composition is 100% by mass.

6. The resin composition according to claim 1, wherein the mass ratio of component (C1) to component (C2) [(C1) component / (C2) component] is 0.01 to 100.

7. The resin composition according to claim 1, wherein component (C2) comprises a maleimide resin represented by the following formula (C2-1). 【Chemistry 1】 (In the formula, n represents a non-negative integer, and * represents a combination.)

8. Furthermore, the resin composition according to claim 1, further comprising (D) an inorganic filler.

9. Furthermore, the resin composition according to claim 1, further comprising (E) an organic filler.

10. Furthermore, the resin composition according to claim 1, further comprising (F) a thermoplastic resin.

11. Furthermore, the resin composition according to claim 1, further comprising (G) a curing accelerator.

12. The resin composition according to claim 1, wherein the dielectric loss tangent (Df) of the cured resin composition is less than 0.0050 when measured at 150 GHz and 90°C.

13. A resin composition according to any one of claims 1 to 12, for use as an insulating layer for a circuit board.

14. A resin sheet comprising a support and a layer of the resin composition according to any one of claims 1 to 12 provided on the support.

15. The resin sheet according to claim 14, wherein the support is a thermoplastic resin film or a metal foil.

16. A cured product of the resin composition according to any one of claims 1 to 12.

17. A circuit board comprising an insulating layer having a cured product of the resin composition according to any one of claims 1 to 12.

18. A semiconductor device comprising the circuit board described in claim 17.

Citation Information

Patent Citations

  • Epoxy resin composition

    JP2010090238A

  • resin composition

    JP6992333B2